Accelerated climate-induced risks of nitrogen-loss from agricultural catchments: Empirical modelling of extreme weather events using climate change scenarios - G. Ezzati; P. Mellander; J. Ortega; B. Fan; C. Murphy (Water Research, 2027)

Asymmetric above- and below-ground interactions: Light availability drives root morphogenesis and productivity in maize–soybean intercropping - Binbin Qiang; Zinan Yan; Xinbo Zhang; Zhen Fan; Juanjuan Zhang; Mengwei Cheng; Yulin Wu; Benjie C. Timbang; Tie Cai; Enke Liu; Xining Zhao; Xiaolong Ren; et al. (Soil and Tillage Research, 2026)

Carbon cloth-mediated direct interspecies electron transfer effect on the intensification mechanism of high-load codigestion dynamic membrane bioreactors - Bao-Shan Xing; Yi-Fan Wu; Yi Zhang; Xiaochang C. Wang; Yu-You Li; Rong Chen (Water Research, 2026)

Petrogenesis of late carboniferous adakitic dikes and granodiorites in the Chinese Altai, NW China: Implications for lower crustal melting and slab roll-back - Shuaiyu Guo; Jiyuan Yin; Mike Fowler; Andrew C. Kerr; Yunchuan Zeng; Zaili Tao; Fan Yang; Jianjun Zhang; Tao Wang; Wenjiao Xiao (Lithos, 2026)

Isochronous rhythms signal male–male competition in an Asian langur - Yinshu Liu; Michael J. Lawes; Zhong Cao; Cyril C. Grueter; Qihai Zhou; Penglai Fan (Animal Behaviour, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Calcium dysregulation in neurovascular function in Alzheimer’s disease: mechanisms, therapeutic targets - Yvan Hanscom-Trofy; Andrew Gregory; Gilbert C. Morgan; Hongwei Yu; Rui Dong; Fan Fan (GeroScience, 2026)

Controlled simulation of oxic-anoxic transition zone in the vadose zone by in situ redox monitoring - Chongyang WANG; Islam M. RADWAN; Jianzhou HE; Yiwen ZHU; Yujie MEN; Dimin FAN; Kenneth C. CARROLL; Dengjun WANG (Pedosphere, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Petrogenesis of Late Triassic adakitic rocks and basalts from the southern Lhasa: Insights into subduction initiation of Neo-Tethys - Cheng Li; Lin Ma; Andrew C. Kerr; Wei Dan; Qiang Wang; Zhiwei Yu; Wei Qiao; Rui Pu; Fan Yang (Lithos, 2026)

Small skeletal fossils associated with Archaeocyath reefs from the Xiannüdong Formation (Cambrian Series 2), southern Shaanxi, China - Baopeng Song; Fan Liu; Jiayue Wang; Mei Luo; Yue Liang; Yazhou Hu; Jingliang Zhao; Lars E. Holmer; Luke C. Strotz; Zhifei Zhang (Palaeobiodiversity and Palaeoenvironments, 2026)
Improved understanding of both the Small Skeletal Fossil (SSF) assemblages and archaeocyath reefs of the early Cambrian Period is important to best elucidate the evolution of early marine ecosystems during the Cambrian Radiation. To address this issue, we investigate the well-preserved SSF fauna associated with archaeocyaths of the early Cambrian Xiannüdong Formation (Dayingcun Section, Nanzheng area, southern Shaanxi). The Xiannüdong fossil assemblage includes sphenothallids, archaeocyaths, brachiopods, bradoriids, hyoliths, helcionelloid molluscs, trilobite sclerites, lobopods, tommotiids, chancelloriids, as well as echinoderm plates. Thin-section analysis, field observations and examination of fossil material indicate the Xiannüdong Formation assemblage consists primarily of an archaeocyath- Sphenothallus dominated ecosystem from a well-structured shallow-water mixed shelf featuring oolite shoals, archaeocyath reefs, adjacent fossiliferous allochthonous floatstone and bioclastic grain-packstone. The fossil assemblage reflects a benthic community which has not been previously described from other Cambrian reef strata of the Yangtze Platform. This unique community indicates that complex reef ecosystems were already present in the early Cambrian in this palaeogeographic region.

Genome wide association analysis and association of genetic risk and lifestyle with upper gastrointestinal cancer among an endoscopy-screened cohort in China - Feifan He; Xianhui Ran; Hao Jiang; Zhiyuan Fan; Yueying Zhang; Jinwu Wang; Changqing Hao; Guohui Song; Yanwei Gong; Yanyan Li; Xinqing Li; Ru Chen; et al. (Science Bulletin, 2026)

A pH-responsive N-heterocyclic carbene stabilized AuPdH nanoplatform for integrated photothermal and hydrogen-mediated biofilm eradication - Fan Wu; Lu Yuan; Yaran Wang; Siran Wang; Linqi Shi; Yong Liu; Yijin Ren; Henny C. van der Mei; Yuanfeng Li (Chemical Engineering Journal, 2026)

Global negative effects of fire on soil fauna communities vary with geographic factors and taxonomic groups - Dixin Chen; Xin Peng; Matthias C. Rillig; Lars Vesterdal; Yan Peng; Qiqian Wu; Zimin Li; Petr Heděnec; Yuexin Fan; Xiangyin Ni; Fuzhong Wu; Kai Yue (Plant and Soil, 2026)

Disentangling litter decomposition trajectories in streams: Ecological insights from a global multimodel analysis - Kai Yue; Matthias C. Rillig; Koenraad Van Meerbeek; Siying Chen; Qiqian Wu; Yan Peng; Kun Guo; Zimin Li; Xin Peng; Yuexin Fan; Nannan An; Xiangyin Ni; et al. (Ecology, 2026)
Stream litter decomposition is a key ecosystem function commonly modeled using a single exponential decay function. However, the flow‐driven nature of stream environments may lead to temporally heterogeneous decay dynamics that are poorly captured by this approach. Here, we evaluated the decomposition process of leaf litter in streams with four decomposition models (single exponential, double exponential, asymptotic, and Weibull) using 523 time series observations across the globe. Results showed that (1) the single exponential model provides a simple and reliable description of litter decomposition dynamics and captures a broad temporal pattern of mass loss; (2) double exponential and asymptotic models were applicable to only a subset of observations, whereas the Weibull model showed relatively consistent applicability across datasets; and (3) climate zone, leaf type, litterbag mesh size, and stream water temperature emerged as the key factors associated with decomposition parameters from different models. Overall, our results suggest that the single exponential model provides a robust description of stream litter decomposition, whereas alternative formulations such as the Weibull model could provide complementary views of decomposition dynamics in stream ecosystems.

Effective science communication in the face of water crises: a community perspective on challenges and best practice in HELPING - Christina Orieschnig; Soham Adla; Kwok Pan Chun; Saumya Srivastava; Khosro Morovati; Ben C. Howard; Thanti Octavianti; José Gescilam Uchôa; Zheng Duan; Paola Mazzoglio; Anandharuban Panchanathan; Borbála Széles; et al. (Hydrological Sciences Journal, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Corrigendum to “Oxidative chemical beneficiation of low-quality coals under low-energy ultrasonic and microwave irradiation: An environmental-friendly approach” [J. Environ. Chem. Eng., 9 (2021) 104830] - Monikankana Saikia; Tonkeswar Das; James C. Hower; Luis F.O. Silva; Xing Fan; Binoy K. Saikia (Journal of Environmental Chemical Engineering, 2026)

Activated carbon enhanced superhydrophobic thermally rearranged nanofibrous membranes for direct contact membrane distillation - Seungju Kim; Anniza C. Augusty; Linhua Fan; Zongli Xie (Chemical Engineering Journal, 2026)

Potential for improving micronutrient supply and environmental sustainability by using underutilized crops in China - Yijun Li; Johanna C. Gerdessen; Wopke van der Werf; Anneleen Kuijsten; Sander de Leeuw; Wen-Feng Cong; Shenggen Fan; Edith J.M. Feskens; Tjeerd Jan Stomph (Global Food Security, 2026)

An effective method for recovering rat spermatogonial stem cells from frozen rat testis cells - Fan Yang; Yaru Li; Mary R. Avarbock; Eoin C. Whelan; Ralph L. Brinster (Cryobiology, 2026)

PTUPB improves cognitive function in Alzheimer’s disease associated with enhancing cerebral vascular myogenic response and attenuating vascular remodeling - Gilbert C. Morgan; Andrew Gregory; Chengyun Tang; Sung Hee Hwang; Jane J. Border; Jing Xu; Yedan Liu; Shan Bai; Tae Jin Lee; Cameron Cantwell; David Bunn; Karen M. Wagner; et al. (GeroScience, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Effect of ciprofloxacin on performance, antibiotic resistance genes, and microbial communities in mesophilic anaerobic codigestion enriched with Methanosarcina and a recovery strategy after collapse - Bao-Shan Xing; Yong-Ning Feng; Su Li; Liguo Wan; Yi-Fan Wu; Xiaochang C. Wang; Rong Chen; Yu-You Li (Chemical Engineering Journal, 2026)

Mid-Seral Thinned Stands in Pacific Northwest Coastal Forests Show Enhanced Floral and Bee Diversity without Increased Parasite Prevalence in Wild Bees - Jesse J. Fan Brown; Katie Moriarty; Rose McDonald; Lincoln R. Best; Jocelyn F. Zorn; Lauren C. Ponisio (Journal of Forestry, 2026)
Management practices, such as forest thinning, may support bee communities by increasing the abundance and diversity of floral resources in forest ecosystems. However, these enhancements could also concentrate foraging bees, potentially facilitating disease spread. In this study, we surveyed understory plant and bee communities and the prevalence of bee parasites across forest stands of different ages and management histories in the coastal Pacific Northwest, including early seral stands, two size classes of mid-seral thinned stands, and mature unthinned stands. We found that both categories of thinned stands supported levels of flowering plant diversity and abundance and overall bee abundance comparable to those found in early seral stands, although bee diversity was highest in early seral stands. In contrast, mature stands exhibited substantially less abundant and diverse plant-pollinator communities than early seral stands. Though we expected that thinned stands would primarily affect flowering plants and bees through reduced canopy cover, within thinned stands increased canopy openness was only associated with a modest increase in floral abundance. We did not observe a strong influence of canopy openness on floral diversity or bee diversity and abundance. The prevalence of the common parasite genus Crithidia spp. was not strongly related to bee or floral community characteristics but was negatively related to bumble bee foraging distance capacity. These findings suggest that thinned forests have enhanced forage opportunities for bees but do not exacerbate the spread of disease—offering a promising management strategy for sustaining healthy pollinator populations in restored forest ecosystems.

Enhancing Floral Resources for Pollinators in Harvested Conifer Forests of the Pacific Northwest - Rose McDonald; Jesse Fan Brown; Rebecca A. Hayes; Nicole Martínez-Llaurador; Peg Boulay; Katie Moriarty; Lauren C. Ponisio (Journal of Forestry, 2026)
Harvested forests have the potential to support pollinator conservation, particularly when enhanced with native flowers, yet their conservation value remains largely untapped and undetermined. Because bee diversity and abundance are closely linked to the diversity and abundance of flowers, our study examined the effectiveness of floral enhancements seeded in wildfire-affected harvested forests in Oregon’s Cascade Mountains, US. We assessed the richness, abundance, cover, floral availability, and persistence of 20 native plant species sown in two contexts: burned slash piles and harvested forest stands. We also compared floral abundance and richness of pollinator-visited floral species in enhanced areas to unaltered areas within stands. We found that sowing native seeds into burned slash piles was an effective strategy for establishing floral enhancements, supporting greater species richness, plant abundance, cover, and floral abundance than enhancements seeded directly into harvested stands. Floral enhancements in burned slash piles persisted for at least three years, providing statistically significantly more pollinator-visited floral resources than unenhanced areas within the stand. Averaging across the second and third years post-seeding, these enhancements supported 5.3 times more pollinator-visited floral species and 8.9 times more total blooms per unit area than unenhanced harvested stands. Compared to unenhanced burned slash piles, enhancements produced 8.2 times more pollinator-visited floral species and 51 times more flowers per unit area. Study implications: Our findings highlight the potential of seeding floral enhancements in burned slash piles as a practical strategy for integrating pollinator conservation into forest management practices. Our approach proved more effective than seeding directly into harvested stands, where competition from existing vegetation and weedy species diminished enhancement success. Successful germination and growth of native flowering plants in burned slash piles, coupled with the persistence of several native species over multiple years, suggested this method may provide valuable resources for increasing stand biodiversity, including direct opportunities for benefiting pollinator conservation.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

A shift in ocean circulation drives variations in paleoproductivity in the North Pacific Ocean - Yongzhi Chu; Xiaohu Li; Liang Yi; Yanhui Dong; Ruifang C. Xie; Zedong Fan; James R. Hein; Susan H. Little; Yu Liu; Hiroyuki Matsuzaki; Weiyan Zhang; Xingwei Meng; et al. (Earth and Planetary Science Letters, 2025)

Enhanced removal of p-nitrophenol using co-pyrolysis biochar: performance evaluation and mechanistic insights - Y. Liu; Z. H. Jiang; A. A. Siyal; C. B. Zhou; C. L. Liu; Y. W. Zhang; B. Yao; L. Chao; D. K. Fan; L. G. Ma; C. Y. Liu; J. J. Dai (International Journal of Environmental Science and Technology, 2025)

Polycyclic aromatic hydrocarbons (PAHs) in soils from a shale gas exploitation area in China: Quantitative sources and risk analysis using an improved hybrid model - Junwu Xiong; Xi Fan; Xiuwen Yang; Huanfang Huang; Chaojie Qin; Chang Pu; Yuan Zhang; Dacong Yin; Wei Liu; Shihua Qi; Kevin C. Jones; Wei Chen (Journal of Hazardous Materials, 2025)

Multifunctional hierarchical BN/MXene-Fe3O4 aerogel for efficient thermal management and ultra-broadband microwave absorption - Xin-Miao Liang; Qi-Fan Xuan; Hong-Hao Li; Peijia Ding; Yu Zhang; Martin C. Koo; Chen-Ming Liang; Shu-Hao Yang; Pei-Yan Zhao; Dongfeng Zhang; Guang-Sheng Wang (Chemical Engineering Journal, 2025)

Evolution of unfrozen water distribution in sandstone pores of varying sizes during freeze-thaw cycles with consideration of moisture recharge - L. F. Fan; C. M. Ma; B. Qiu (Bulletin of Engineering Geology and the Environment, 2025)

Life-history-dependent and seasonally varying distribution patterns of Atlantic bigeye (Priacanthus arenatus) in western African coast - Fengyuan Shen; Yuqing Zhang; Chunlei Feng; Taichun Qu; Ruiliang Fan; Zhixuan Feng; Hanfeng Zheng; Hui Xu; Hewei Liu; Shuai Li; Xiumei Fan; Xue Wang; et al. (Frontiers in Marine Science, 2025)
Understanding spatiotemporal distribution patterns of fish across life history stages is critical for sustainable fishery management, particularly in data-poor regions such as the extensive yet poorly explored western African coastal regions. This study investigates the distribution patterns and ontogenetic habitat shifts of Atlantic bigeye ( Priacanthus arenatus ) at various life stages on the coast of Sierra Leone using data from twelve cruises conducted between 2019 and 2021. Our results reveal distinct life-stage partitioning across multiple life stages of Atlantic bigeye. Juveniles (<60 mm body length) predominantly distribute in the pelagic waters beyond the continental shelf. As individuals reach a body length of approximately 60 mm, they enter the sub-adult stage, characterized by the onset of gonad development and a noticeable migration to demersal areas within the continental shelf. Adults (≥150 mm body length) are basically demersal as populations primarily distribute in demersal areas within the continental shelf. Our observations also suggest that juvenile Atlantic bigeye exhibits capture peaks: one prior to the rainy season (April–May) and the other after the rainy season (September–October), suggesting a potential correlation with spawning. Moreover, the extensive offshore distribution of juveniles beyond the continental shelf appears to be closely associated with seasonal river plume spread, potentially reflecting a behavioral adaptation to utilize oceanic dispersal pathways during periods of enhanced freshwater input. These findings fill a critical knowledge gap and provide a scientific basis for fisheries research and management of this species in western African waters.

Long-Term Significant Wave Height Forecasting in the Western Atlantic Ocean Using Deep Learning - Lu Zhang; Fan Jiang; Limin Huang; Dina Silva; Wenyang Duan; C. Guedes Soares (Journal of Marine Science and Engineering, 2025)
This study presents a significant wave height correction model using deep learning techniques to enhance long-term wave forecast capabilities. The model utilises buoy measurements to assess the forecasting accuracy of the ECMWF 15-day forecast of significant wave height in the western Atlantic Ocean under various input conditions. The performance of different deep learning methods in modelling the wave forecast error is compared. The model predictions are validated against buoy data, revealing that the forecasting accuracy of the various deep learning methods is comparable. In addition, the model’s adaptability is examined for varying locations and water depths within the study area. The results demonstrate that the proposed method significantly improves the accuracy of the 15-day wave height forecasting and exhibits good adaptability to a vast sea area.

Stroke Mechanisms in Intracranial Atherosclerotic Disease: A Modified Classification System and Clinical Implications - Shuang Li; Xuan Tian; Xueyan Feng; Bonaventure Ip; Hing Lung Ip; Jill Abrigo; Lina Zheng; Yuying Liu; Yu Liu; Ziqi Li; Tingjun Liang; Karen K. Y. Ma; et al. (Translational Stroke Research, 2025)
Background In patients with symptomatic intracranial atherosclerotic stenosis (sICAS), recent evidence has suggested an association between artery-to-artery embolism (AAE) and cortical borderzone (CBZ) infarcts. Methods We recruited patients with 50–99% anterior-circulation sICAS in this cohort. Stroke mechanisms were categorized as isolated parent artery atherosclerosis occluding penetrating artery (PAO), isolated AAE, isolated hypoperfusion, and mixed mechanisms, using two classification systems. In Classification I, the probable stroke mechanisms of internal borderzone and CBZ infarcts were both hypoperfusion, which were respectively hypoperfusion and AAE in Classification II. Other classification criteria were the same. We investigated and compared the predictive values of the two systems in predicting 90-day and 1-year recurrent ischemic stroke in the same territory (SIT). Results Among 145 patients (median age 62 years), 101 (69.7%) were males. We found significant difference in the proportions of baseline stroke mechanisms between these two systems (p < 0.001). Eleven (7.6%) and 19 (13.1%) patients respectively had 90-day or 1-year recurrent SIT. Classification II better predicted the risk of 90-day recurrent SIT than Classification I, when patients were divided into 4 groups according to baseline stroke mechanisms (p = 0.029), or by the presence of hypoperfusion (p < 0.001). The two classification systems had comparable predictive values for 1-year recurrent SIT. Conclusions In medically treated sICAS patients, considering AAE rather than hypoperfusion as the stroke mechanism for CBZ infarcts could better predict early recurrent SITs.

Belowground persistence types relevant to severe disturbance - Jitka Klimešová; Daniel C. Laughlin; Frances Siebert; Joana Bergmann; Shersingh Joseph Tumber-Dávila; Karl Andraczek; Aline B. Bombo; Helge Bruelheide; Ying Fan; Grégoire T. Freschet; Justus Hennecke; Cody Coyotee Howard; et al. (Trends in Plant Science, 2025)

A metagenomics-based approach to understanding the transmission of healthcare-associated antimicrobial resistance in Pakistan - Muhammad Umer Asghar; Yuting Zhai; Ting Liu; Peixin Fan; Noor Ul Ain; Arsalan Haseeb Zaidi; Muhammad Tariq; Raul C. Mainar-Jaime; Kwangcheol C. Jeong (Journal of Hazardous Materials, 2025)

Hydrogen-rich syngas production from the steam co-gasification of low-density polyethylene and coal refuse - Sittichai Natesakhawat; Jennifer Weidman; Nicholas C. Means; Bret H. Howard; Fan Shi; Jonathan Lekse; McMahan Gray; Ping Wang (Fuel, 2025)

Metabolism and hypoxia tolerance of the endangered white abalone (Haliotis sorenseni): Implications for conservation and restoration efforts - Stephanie J. Fan; Taylor R. Smith; Nasseer Idrisi; John R. Hyde; Nicholas C. Wegner (Journal of Experimental Marine Biology and Ecology, 2025)

Cretaceous to Cenozoic Magmatic and Crustal Evolution of the Pamir-West Kunlun Orogenic Belt - Fan Yang; Jiyuan Yin; Mike Fowler; Andrew C. Kerr; Zaili Tao (Journal of Earth Science, 2025)

A plant virus causes symptoms through the deployment of a host-mimicking protein domain to attract the insect vector - Man Gao; Emmanuel Aguilar; Borja Garnelo Gómez; Laura Medina-Puche; Pengfei Fan; Irene Ontiveros; Shaojun Pan; Huang Tan; Hua Wei; Edda von Roepenack-Lahaye; Na Chen; Xiao-Wei Wang; et al. (Molecular Plant, 2025)

National Inventory of Plastic Mulch Residues in Chinese Croplands From 1993 to 2050 - Jizhao Dai; Can Hu; Markus Flury; Yao Huang; Matthias C. Rillig; Dechang Ji; Jianwei Peng; Jiangchi Fei; Qing Huang; Youcai Xiong; Ning Yang; Davey L. Jones; et al. (Global Change Biology, 2025)
Agricultural plastic mulch films are a major source of plastic pollution of croplands. In China, which uses about 68% of the plastic mulch film produced globally (ca. 1.4 million tonnes y −1 ), soils have been heavily contaminated with mulch fragments. Here, we collected a national dataset of macroplastic residues (> 5 mm) in soil, including 3145 sampling sites, and provincial plastic film usage from 1992 to 2019 in China, and we established a linear model between the residue amount and historical cumulative usage within each province. Using the model, we quantified the amount of macroplastic residues in Chinese croplands on a national scale during the past 30 years and predict plastic pollution until 2050. Our results reveal the total national amount of plastic mulch residue in 2020 to be 2.07 million tonnes with a 95% CI of [1.67, 2.58]. This accumulated amount of plastic in Chinese soils roughly equals the annual amount of plastic films used globally (2.08 million tonnes in 2018) and is about 8% of national historically used plastic mulch film (27.3 million tonnes) remaining in soil as legacy plastic. Plastic concentrations in Chinese croplands in 2020 range from 7.7 kg ha −1 in Anhui to 399 kg ha −1 in Xinjiang, with an average value of 119 kg ha −1 (equivalent to 0.03 g kg −1 soil). We predict that the total amount and average concentration of plastic residues in Chinese croplands will reach 6.24 million tonnes and 357 kg ha −1 (equivalent to 0.1 g kg −1 soil) in 2050 under current plastic usage. There is an urgent need for regulatory actions to control plastic pollution in Chinese agriculture.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Characterization of the reproductive tract microbiome in subfertile mares: A comprehensive analysis across anatomical sites and estrous cycle phases - N. Schultz; A. Reeves; C. Runyan; Z. Contreras; J.L. Leatherwood; P. Fan; R.E. Martinez (Journal of Equine Veterinary Science, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Skeletal muscle-specific Bambi deletion induces hypertrophy and oxidative switching coupling with adipocyte thermogenesis against metabolic disorders - Xiangping Yao; Xudong Mai; Ye Tian; Yifan Liu; Guanghui Jin; Ze Li; Shujie Chen; Xiaoshuang Dai; Liujing Huang; Zijing Fan; Guihua Pan; Xiaohan Pan; et al. (Science China Life Sciences, 2025)

M8OI toxicity is associated with an inhibition of ubiquinone reduction by complex I in the mitochondrial electron transport chain - Tarek M. Abdelghany; Jessica Bosak; Alistair C. Leitch; Alex Charlton; Lanyu Fan; Fahad A. Aljehani; Omar H. Alkhathami; Shireen A. Hedya; Satomi Miwa; Agnieszka K. Bronowska; Judy Hirst; Matthew C. Wright (Chemosphere, 2025)

Dispersing zeolite in technical catalyst particles using a top spray fluidized bed reactor for methanol to hydrocarbons reaction - Ali M. Alkadhem; Hend Omar Mohamed; Torsten Hoffmann; Jiyuan Fan; Valentina E. Musteata; Stephen C. Ogg; Javier Ruiz-Martinez; Evangelos Tsotsas; Pedro Castaño (Chemical Engineering Journal, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Impact thermal and calcium oxide pretreatment on the anaerobic digestion of food waste: performance and carbon emissions - Y. Liu; L. Tian; W. Qiu; W. Sun; C. Pan; G. Fan; Q. Cheng (International Journal of Environmental Science and Technology, 2025)

Toward an integrated pantropical ocean observing system - Gregory R. Foltz; Yassir A. Eddebbar; Janet Sprintall; Antonietta Capotondi; Sophie Cravatte; Peter Brandt; Adrienne J. Sutton; Tamaryn Morris; Juliet Hermes; Clive R. McMahon; Michael J. McPhaden; Lev B. Looney; et al. (Frontiers in Marine Science, 2025)
Global climate is regulated by the ocean, which stores, releases, and transports large amounts of mass, heat, carbon, and oxygen. Understanding, monitoring, and predicting the exchanges of these quantities across the ocean’s surface, their interactions with the atmosphere, and their horizontal and vertical pathways through the global oceans, are key for advancing fundamental knowledge and improving forecasts and longer-term projections of climate, weather, and ocean ecosystems. The existing global observing system provides immense value for science and society in this regard by supplying the data essential for these advancements. The tropical ocean observing system in particular has been developed over decades, motivated in large part by the far-reaching and complex global impacts of tropical climate variability and change. However, changes in observing needs and priorities, new challenges associated with climate change, and advances in observing technologies demand periodic evaluations to ensure that stakeholders’ needs are met. Previous reviews and assessments of the tropical observing system have focused separately on individual basins and their associated observing needs. Here we provide a broader perspective covering the tropical observing system as a whole. Common gaps, needs, and recommendations are identified, and interbasin differences driven by socioeconomic disparities are discussed, building on the concept of an integrated pantropical observing system. Finally, recommendations for improved observations of tropical basin interactions, through oceanic and atmospheric pathways, are presented, emphasizing the benefits that can be achieved through closer interbasin coordination and international partnerships.

Inhibition of soluble epoxide hydrolase ameliorates cerebral blood flow autoregulation and cognition in alzheimer's disease and diabetes-related dementia rat models - Chengyun Tang; Jane J. Border; Huawei Zhang; Andrew Gregory; Shan Bai; Xing Fang; Yedan Liu; Shaoxun Wang; Sung Hee Hwang; Wenjun Gao; Gilbert C. Morgan; Jhania Smith; et al. (GeroScience, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Light iron isotopes in high-silica granites record fluid evolution in magmatic-hydrothermal systems - Qi-Wei Li; Qiang Wang; Lin Ma; Andrew C. Kerr; Jing-Jing Fan; Jun-Hong Zhao; Hai-Ou Gu; Wei Wang; Zhi-Kun Su (Geochimica et Cosmochimica Acta, 2025)

Angiopoietin-like protein 2 inhibits thrombus formation - Tiantian Zhang; Mingliang Zhang; Lingyu Guo; Dongsheng Liu; Kandi Zhang; Changlong Bi; Peng Zhang; Jin Wang; Yuqi Fan; Qing He; Alex C. Y. Chang; Junfeng Zhang (Molecular and Cellular Biochemistry, 2025)
Acute myocardial infarction is mainly caused by a lack of blood flood in the coronary artery. Angiopoietin-like protein 2 (ANGPTL2) induces platelet activation and thrombus formation in vitro through binding with immunoglobulin-like receptor B, an immunoglobulin superfamily receptor. However, the mechanism by which it regulates platelet function in vivo remains unclear. In this study, we investigated the role of ANGPTL2 during thrombosis in relationship with ST-segment elevation myocardial infarction (STEMI) with spontaneous recanalization (SR). In a cohort of 276 male and female patients, we measured plasma ANGPTL2 protein levels. Using male Angptl2 -knockout and wild-type mice, we examined the inhibitory effect of Angptl2 on thrombosis and platelet activation both in vivo and ex vivo. We found that plasma and platelet ANGPTL2 levels were elevated in patients with STEMI with SR compared to those in non-SR (NSR) patients, and was an independent predictor of SR. Angptl2 deficiency accelerated mesenteric artery thrombosis induced by FeCl 3 in Angptl2 –/– compared to WT animals, promoted platelet granule secretion and aggregation induced by thrombin and collogen while purified ANGPTL2 protein supplementation reversed collagen-induced platelet aggregation. Angptl2 deficiency also increased platelet spreading on immobilized fibrinogen and clot contraction. In collagen-stimulated Angptl2 –/– platelets, Src homology region 2 domain–containing phosphatase (Shp)1-Y564 and Shp2-Y580 phosphorylation were attenuated while Src, Syk, and Phospholipase Cγ2 (PLCγ2) phosphorylation increased. Our results demonstrate that ANGPTL2 negatively regulated thrombus formation by activating ITIM which can suppress ITAM signaling pathway. This new knowledge provides a new perspective for designing future antiplatelet aggregation therapies.

Relational characteristics and dynamics between high-tech firms in the Pearl River Delta and the empowerment for technological innovation by Hong Kong - Jili Xu; Anthony G. O. Yeh; George C. S. Lin; Xingjian Liu; Fan Fiona Yang; Zixin Luo (Journal of Geographical Sciences, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Delivering scientific evidence for global policy and management to ensure ocean sustainability - K. Evans; J. O. Schmidt; K. Appeaning Addo; M. J. Bebianno; D. Campbell; J. Fan; R. Gonzalez-Quiros; E. Y. Mohammed; M. G. Shojaei; V. Smolyanitsky; C.-I. Zhang (Sustainability Science, 2025)
Life depends on the ocean, with societal health, cultural systems and national economies reliant on ocean processes and resources. As ocean resources are used, and humans continue to drive climate change, the benefits from the ocean to society are being diminished. Science must meet the needs of policy and deliver to decision makers the information and tools for identifying pathways that support continued delivery of the benefits society derives from the ocean, whilst minimising impacts. This is crucial if the world’s nations are to meet the goals and targets they have set under international agreements. Here, we outline how a global assessment that focuses specifically on the ocean, the World Ocean Assessment, is linking science to the governments of the world and their policies within an internationally mandated framework. In doing so, we identify key elements that are needed for facilitating engagement by decision makers and uptake of knowledge, and the pathways taken by the assessment in implementing them. We also provide insights into the evolution that the World Ocean Assessment has undertaken over its first three cycles to progress its goal of enhancing the scientific basis of policymaking. We identify the challenges in delivering science to policy at a global scale and the work that still needs to be done in filling gaps to achieve a coordinated, comprehensive mechanism for connecting science with policy and ensuring future sustainability of the ocean.

Enhanced H2S removal efficiency using CuO/Al2O3 catalyst impregnated with Ca(NO3)2: Influence of calcination temperature and mechanistic insights - Mengxue Yin; Suresh C. Pillai; Hailong Wang; Feiyue Fan; Hong Hou (Process Safety and Environmental Protection, 2024)

Comparison of the short- and long-term effects of zinc ions on the anaerobic mesophilic co-digestion of food waste and waste activated sludge: Digester performance, antibiotic resistance gene reduction and the microbial community - Bao-Shan Xing; Yi-Meng Su; Yu-Lin Fu; Yi-Fan Wu; Chen-Hao Yan; Xiaochang C. Wang; Yu-You Li; Rong Chen (Journal of Hazardous Materials, 2024)

Unmanned Surface Vessel–Unmanned Aerial Vehicle Cooperative Path Following Based on a Predictive Line of Sight Guidance Law - Hugan Zhang; Jiaming Fan; Xianku Zhang; Haitong Xu; C. Guedes Soares (Journal of Marine Science and Engineering, 2024)
This paper explores the cooperative control of unmanned surface vessels (USVs) and unmanned aerial vehicles (UAVs) in maritime rescue and coastal surveillance. The USV-UAV system faces challenges of disturbances and substantial inertia-induced overshooting during path following. A novel position prediction line of sight (LOS) guidance law is proposed to address these issues for USV path following control. Radial basis function-based neural networks (RBF-NNs) are used to estimate disturbances, and a high-order differentiator is used to design a velocity observer for unknown USV velocity. The UAV control system employs proportional–derivative (PD) control with feedforward compensation for quadrotor control design and utilizes a finite-time converging third-order differentiator to differentiate non-continuous functions. The simulation results demonstrate strong robustness in the proposed USV-UAV cooperative control algorithm. It achieves path following control in the presence of wind and wave disturbances and exhibits minimal overshoot.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Wave attenuation coefficient and wave number of high-temperature granite after water cooling and air cooling - Q. H. Yang; K. C. Yang; G. Y. Li; L. F. Fan; X. L. Du (Bulletin of Engineering Geology and the Environment, 2024)

Methylimidazolium ionic liquids - A new class of forever chemicals with endocrine disrupting potential - Tarek M. Abdelghany; Shireen Hedya; Alex Charlton; Lanyu Fan; Narges Fazili; Ben Air; Alistair C. Leitch; Martin Cooke; Agnieszka K. Bronowska; Matthew C. Wright (Chemosphere, 2024)

P08-05 The Role and mechanism of O-GlcNAcylation in abnormalities of oocyte maturation and early embryonic development caused by PFOS exposure - Z. Wu; Q. Yuan; H. Qian; S. Han; Q. Xu; Y. Xia; Y. Fan; C. Lu (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Groundwater solutes influence the adsorption of short-chain perfluoroalkyl acids (PFAA) to colloidal activated carbon and impact performance for in situ groundwater remediation - Rachel A. Molé; Adriana C. Velosa; Grant R. Carey; Xitong Liu; Guangbin Li; Dimin Fan; Anthony Danko; Gregory V. Lowry (Journal of Hazardous Materials, 2024)

A study at the wildlife-livestock interface unveils the potential of feral swine as a reservoir for extended-spectrum β-lactamase-producing Escherichia coli - Ting Liu; Shinyoung Lee; Miju Kim; Peixin Fan; Raoul K. Boughton; Christina Boucher; Kwangcheol C. Jeong (Journal of Hazardous Materials, 2024)

Photoactive cationic conjugated microporous polymers containing pyrimidine with an ‘adsorption-kill’ antibacterial strategy for infected wound healing - Ga Liu; Shengfei Bao; Jiahao Shi; Chunyu Xie; Fuying Liao; Lingshuang Wang; Fan Zheng; Rui L. Reis; Subhas C. Kundu; Bo Xiao; Xiao Yang; Lian Duan (Chemical Engineering Journal, 2024)

Cerebral Hemodynamics Underlying Artery-to-Artery Embolism in Symptomatic Intracranial Atherosclerotic Disease - Xueyan Feng; Hui Fang; Bonaventure Y. M. Ip; Ka Lung Chan; Shuang Li; Xuan Tian; Lina Zheng; Yuying Liu; Linfang Lan; Haipeng Liu; Jill Abrigo; Sze Ho Ma; et al. (Translational Stroke Research, 2024)

Reproducible responses of geochemical and microbial successional patterns in the subsurface to carbon source amendment - Jonathan P. Michael; Andrew D. Putt; Yunfeng Yang; Benjamin G. Adams; Kathryn R. McBride; Yupeng Fan; Kenneth A. Lowe; Daliang Ning; Sindhu Jagadamma; Ji Won Moon; Dawn M. Klingeman; Ping Zhang; et al. (Water Research, 2024)

Discriminating milk storage time with mid-infrared spectra combined with machine learning - J. Su; Y. Chen; L. Nan; H. Wang; X. Luo; Y. Fan; Y. Zhang; C. Du; N. Gengler; S. Zhang (International Dairy Journal, 2024)

Biochar and surfactant synergistically enhanced PFAS destruction in UV/sulfite system at neutral pH - Jianzhou He; Melissa Boersma; Ziteng Song; Samuel Krebsbach; Dimin Fan; Evert C. Duin; Dengjun Wang (Chemosphere, 2024)

Shifts in plant resource use strategies across climate and soil gradients in dryland steppe communities - Baoli Fan; Andrea C. Westerband; Ian J. Wright; Pengfei Gao; Nana Ding; Dongxia Ai; Tingting Tian; Xiang Zhao; Kun Sun (Plant and Soil, 2024)

Addressing the gap: advancements in flow forecasting systems for small mountainous catchments - M. R. Fagundes; F. M. Fan; C. H. A. Gama; K. Campagnolo; M. A. Paixão; M. Kobiyama (Natural Hazards, 2024)

Effects of lianas on forest biogeochemistry during their lives and afterlives - Gbadamassi G. O. Dossa; Hong‐Lin Li; Bo Pan; Tial C. Ling; Douglas A. Schaefer; Mareike Roeder; Denis M. Njoroge; Juan Zuo; Liang Song; Bismark Ofosu‐Bamfo; Stefan A. Schnitzer; Rhett D. Harrison; et al. (Global Change Biology, 2024)
Climate change and other anthropogenic disturbances are increasing liana abundance and biomass in many tropical and subtropical forests. While the effects of living lianas on species diversity, ecosystem carbon, and nutrient dynamics are receiving increasing attention, the role of dead lianas in forest ecosystems has been little studied and is poorly understood. Trees and lianas coexist as the major woody components of forests worldwide, but they have very different ecological strategies, with lianas relying on trees for mechanical support. Consequently, trees and lianas have evolved highly divergent stem, leaf, and root traits. Here we show that this trait divergence is likely to persist after death, into the afterlives of these organs, leading to divergent effects on forest biogeochemistry. We introduce a conceptual framework combining horizontal, vertical, and time dimensions for the effects of liana proliferation and liana tissue decomposition on ecosystem carbon and nutrient cycling. We propose a series of empirical studies comparing traits between lianas and trees to answer questions concerning the influence of trait afterlives on the decomposability of liana and tree organs. Such studies will increase our understanding of the contribution of lianas to terrestrial biogeochemical cycling, and help predict the effects of their increasing abundance.

Modeling and experimental validation of the time-temperature profile, pectin methylesterase inactivation, and ascorbic acid degradation during the continuous flow microwave-assisted pasteurization of orange juice - Kaiky C. Amaro; Guilherme Russo; Danielle Lu Fan; Jorge A.W. Gut; Carmen C. Tadini (Food and Bioproducts Processing, 2024)

Deciphering the synergistic effects of photolysis and biofiltration to actuate elimination of estrogens in natural water matrix - Fan Huang; Junwang Tang; Like Xu; Luiza C. Campos (Water Research, 2024)

Fractionation of critical metals from authentic acid mine drainage using a multi-bed immobilized amine sorbent setup: A field site study - Walter C. Wilfong; Qiuming Wang; Bret Howard; Phillip Tinker; Karen Johnson; William Garber; Fan Shi; McMahan L. Gray (Journal of Water Process Engineering, 2024)

Exposure to ambient air toxicants and the risk of amyotrophic lateral sclerosis (ALS): A matched case control study - Fan Wu; Angela M. Malek; Jeanine M. Buchanich; Vincent C. Arena; Judith R. Rager; Ravi K. Sharma; John E. Vena; Todd Bear; Evelyn O. Talbott (Environmental Research, 2024)

Synthesis of nano-MgO hybrid SDB hydrophobic catalyst carriers and its adsorption behavior of Fe3+ - Y. Fan; H. R. Peng; C. Li; K. Fu; X. Y. Ren; H. J. Yang; S. D. Lin; C. L. Liu (International Journal of Environmental Science and Technology, 2024)

Characterization and stabilization of incineration fly ash from a new multi-source hazardous waste co-disposal system: field-scale study on solidification and stabilization - Xiaofan Huang; Lei Wang; Gu Fan; Xiaotao Bi; Dahai Yan; Jonathan W. C. Wong; Yuezhao Zhu (Environmental Science and Pollution Research, 2024)

Low temperature selective catalytic oxidation of H2S: Influencing factors, mechanisms and regeneration - Mengxue Yin; Suresh C. Pillai; Nanthi Bolan; Hailong Wang; Hongliang Yin; Zhihao Wu; Yan Zheng; Long Zhao; Feiyue Fan; Hong Hou (Chemical Engineering Journal, 2024)

Diversity and connectedness of brine shrimp viruses in global hypersaline ecosystems - Xuan Dong; Cixiu Li; Yiting Wang; Tao Hu; Fan Zhang; Fanzeng Meng; Meirong Gao; Xuekai Han; Guohao Wang; Jiahao Qin; Hans Nauwynck; Edward C. Holmes; et al. (Science China Life Sciences, 2024)

Effects of Mooring Line with Different Materials on the Dynamic Response of Offshore Floating Wind Turbine - Yushun Lian; Fan Zhong; Jinhai Zheng; Wenxing Chen; Gang Ma; Shan Wang; Solomon C. Yim (Journal of Marine Science and Engineering, 2023)
The influence of mooring systems with lines of different material on the dynamic response of a floating wind turbine is studied using a 5 MW OC4-DeepCwind semi-submersible wind turbine as a representative prototype in this study. Two types of mooring systems were designed using the MoorDyn module in OpenFAST software (v3.1.0): one uses chains, and the other uses a hybrid mooring line composed of chains and high-strength polyethylene (HMPE) ropes. A wind turbine with two types of mooring systems was simulated using the OpenFAST software. The results show that the floating wind turbine moored with the hybrid lines exhibited a larger heave and pitch motion than that moored using chains alone. At the same time, the surge displacement was smaller than that of the wind turbine using chains alone. In terms of mooring line tension, the mean and amplitude values of the hybrid mooring system at the location examined were smaller than those of the chain mooring system. Thus, using HMPE ropes in the mooring system can significantly reduce line loads. In addition, the HMPE ropes used in the floating wind turbine mooring system did not affect the power generation of the wind turbine. This study provides promising support data and observations for applying high-strength polyethylene (HMPE) ropes in mooring systems for floating wind turbines.

Influence of soil organic components on the aniline adsorption mechanism - M. Yan; C. Lu; A. Shengji; Z. Fan; Z. Dading; W. Tong; Z. Shengkun; D. Yunkai; L. Bowen (International Journal of Environmental Science and Technology, 2023)

What controls the availability of organic and inorganic P sources in top- and subsoils? A 33P isotopic labeling study with root exudate addition - Juanjuan Ai; Callum C. Banfield; Guodong Shao; Kazem Zamanian; Tobias Stürzebecher; Lingling Shi; Lichao Fan; Xia Liu; Sandra Spielvogel; Michaela A. Dippold (Soil Biology and Biochemistry, 2023)

Improving the performance of artificial intelligence models using the rotation forest technique for landslide susceptibility mapping - H. Shen; F. Huang; X. Fan; H. Shahabi; A. Shirzadi; D. Wang; C. Peng; X. Zhao; W. Chen (International Journal of Environmental Science and Technology, 2023)

Cellulose δ18O as a hydrological proxy: A case study for willows growing in Indigirka river lowland, Northeastern Siberia - Rong Fan; Trofim C. Maximov; Atsuko Sugimoto (Polar Science, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Porcine spermadhesin AQN-3 binds to negatively charged phospholipids - Karin Müller; Peter Müller; Fan Lui; Pascal D. Kroh; Beate C. Braun (Chemistry and Physics of Lipids, 2023)

Geological controls on the distribution of gas hydrates in the shallow parts of the gas hydrate stability zone – constraints from seafloor drilling off Taiwan - G. Bohrmann; C. Berndt; S. Lin; T.-H. Tu; A.T. Lin; H.-H. Hsu; M.-C. Lai; W.-C. Chi; C. Deusner; J. Elger; K. Wallmann; T. Freudenthal; et al. (Marine and Petroleum Geology, 2023)

Promotion strategies for environmentally friendly packaging: a stochastic differential game perspective - C. Wang; J. Liu; R. Fan; L. Xiao (International Journal of Environmental Science and Technology, 2023)

Recent progress on understanding coronal mass ejection/flare onset by a NASA living with a star focused science team - Mark G. Linton; Spiro K. Antiochos; Graham Barnes; Yuhong Fan; Yang Liu; Benjamin J. Lynch; Andrey N. Afanasyev; C. Nick Arge; Joan Burkepile; Mark C.M. Cheung; Joel T. Dahlin; Marc L. DeRosa; et al. (Advances in Space Research, 2023)

Characteristics of fine and ultrafine aerosols in the London underground - Prashant Kumar; Juan C. Zavala-Reyes; Gopinath Kalaiarasan; Hisham Abubakar-Waziri; Gloria Young; Ian Mudway; Claire Dilliway; Ramzi Lakhdar; Sharon Mumby; Michał M. Kłosowski; Christopher C. Pain; Ian M. Adcock; et al. (Science of The Total Environment, 2023)

Correction to: Wheat straw reduces runoff, sediment yield and flow velocity in sloping farmland under two straw mulching methods - J. Ma; B. Ma; C. Wang; Y. Wang; S. Fan; C. Li (Plant and Soil, 2023)

How can diverse national food and land-use priorities be reconciled with global sustainability targets? Lessons from the FABLE initiative - Aline Mosnier; Guido Schmidt-Traub; Michael Obersteiner; Sarah Jones; Valeria Javalera-Rincon; Fabrice DeClerck; Marcus Thomson; Frank Sperling; Paula Harrison; Katya Pérez-Guzmán; Gordon Carlos McCord; Javier Navarro-Garcia; et al. (Sustainability Science, 2023)
There is an urgent need for countries to transition their national food and land-use systems toward food and nutritional security, climate stability, and environmental integrity. How can countries satisfy their demands while jointly delivering the required transformative change to achieve global sustainability targets? Here, we present a collaborative approach developed with the FABLE—Food, Agriculture, Biodiversity, Land, and Energy—Consortium to reconcile both global and national elements for developing national food and land-use system pathways. This approach includes three key features: (1) global targets, (2) country-driven multi-objective pathways, and (3) multiple iterations of pathway refinement informed by both national and international impacts. This approach strengthens policy coherence and highlights where greater national and international ambition is needed to achieve global goals (e.g., the SDGs). We discuss how this could be used to support future climate and biodiversity negotiations and what further developments would be needed.

Ecophysiological and genomic analyses of a representative isolate of highly abundant Bacillus cereus strains in contaminated subsurface sediments - Jennifer L. Goff; Elizabeth G. Szink; Michael P. Thorgersen; Andrew D. Putt; Yupeng Fan; Lauren M. Lui; Torben N. Nielsen; Kristopher A. Hunt; Jonathan P. Michael; Yajiao Wang; Daliang Ning; Ying Fu; et al. (Environmental Microbiology, 2022)
Bacillus cereus strain CPT56D‐587‐MTF (CPTF) was isolated from the highly contaminated Oak Ridge Reservation (ORR) subsurface. This site is contaminated with high levels of nitric acid and multiple heavy metals. Amplicon sequencing of the 16S rRNA genes (V4 region) in sediment from this area revealed an amplicon sequence variant (ASV) with 100% identity to the CPTF 16S rRNA sequence. Notably, this CPTF‐matching ASV had the highest relative abundance in this community survey, with a median relative abundance of 3.77% and comprised 20%–40% of reads in some samples. Pangenomic analysis revealed that strain CPTF has expanded genomic content compared to other B. cereus species—largely due to plasmid acquisition and expansion of transposable elements. This suggests that these features are important for rapid adaptation to native environmental stressors. We connected genotype to phenotype in the context of the unique geochemistry of the site. These analyses revealed that certain genes (e.g. nitrate reductase, heavy metal efflux pumps) that allow this strain to successfully occupy the geochemically heterogenous microniches of its native site are characteristic of the B. cereus species while others such as acid tolerance are mobile genetic element associated and are generally unique to strain CPTF.

Correction to: Cerebral Microvascular Injury in Patients with Left Ventricular Assist Device: a Neuropathological Study - Tracey H. Fan; Sung‑Min Cho; Richard A. Prayson; Catherine E. Hassett; Randall C. Starling; Ken Uchino (Translational Stroke Research, 2022)

A fungal mycelium elicitor efficiently improved ginsenoside synthesis during adventitious root culture of Panax ginseng - X. L. An; Y. Yu; M. Z. Fan; X. H. Wu; X. F. Li; X. C. Piao; M. L. Lian (Journal of Plant Biochemistry and Biotechnology, 2022)

Field engineering application of agricultural farmland surface runoff pollution treatment by combined bioreactor and constructed wetlands - H. Luo; X. Li; Y. Chen; X. Liu; K. Zhang; X. Fu; B. Jiang; R. Xue; J. Yang; M. Li; X. Li; W. Chen; et al. (International Journal of Environmental Science and Technology, 2022)

Research on soil water content variation in coal mining area based on ground-penetrating radar - W. Zhiyuan; C. Fan; N. Junli; X. Tianxiang (International Journal of Environmental Science and Technology, 2022)

Cerebral Microvascular Injury in Patients with Left Ventricular Assist Device: a Neuropathological Study - Tracey H. Fan; Sung-Min Cho; Richard A. Prayson; Catherine E. Hassett; Randall C. Starling; Ken Uchino (Translational Stroke Research, 2022)

Oyster Aquaculture Site Selection Using High-Resolution Remote Sensing: A Case Study in the Gulf of Maine, United States - Binbin Jiang; Emmanuel Boss; Thomas Kiffney; Gabriel Hesketh; Guillaume Bourdin; Daidu Fan; Damian C. Brady (Frontiers in Marine Science, 2022)
Aquaculture of the eastern oyster, Crassostrea virginica , is an expanding industry in the US, particularly in the Gulf of Maine. High resolution ocean color satellites launched in the last decade potentially provide aquaculture-relevant water-quality parameters at farm scales. However, these parameters, such as temperature, suspended particulate matter (SPM), and Chlorophyll a (Chl a), need to be derived by interested users. Water quality parameters are derived first by applying an atmospheric correction and then estimating the target parameter with a specific algorithm. Here, we use five atmospheric correction schemes and two algorithms to derive SPM and Chl a from the Sentinel 2A&B satellites’ multispectral instrument data. The best estimates of SPM and Chl a are determined by comparison with in situ observations from buoys. Together with SST from Landsat-8, we estimated an Oyster Suitability Index (OSI) along the transects in five estuaries in the Gulf of Maine as well as applied a novel particulate organic matter algorithm, a function of Chl a and SPM in low turbidity estuaries. We then apply the optimal approaches to derive water quality parameters to study five different estuaries in Maine and find that existing high-yield oyster aquaculture farms are found in areas with elevated OSI values. Additionally, we suggest new areas, currently under-exploited, where oyster aquaculture is likely to succeed, showcasing the utility of the approach.

Loss of Neuron Navigator 2 Impairs Brain and Cerebellar Development - Andrea Accogli; Shenzhao Lu; Ilaria Musante; Paolo Scudieri; Jill A. Rosenfeld; Mariasavina Severino; Simona Baldassari; Michele Iacomino; Antonella Riva; Ganna Balagura; Gianluca Piccolo; Carlo Minetti; et al. (The Cerebellum, 2022)
Cerebellar hypoplasia and dysplasia encompass a group of clinically and genetically heterogeneous disorders frequently associated with neurodevelopmental impairment. The Neuron Navigator 2 ( NAV2 ) gene (MIM: 607,026) encodes a member of the Neuron Navigator protein family, widely expressed within the central nervous system (CNS), and particularly abundant in the developing cerebellum. Evidence across different species supports a pivotal function of NAV2 in cytoskeletal dynamics and neurite outgrowth. Specifically, deficiency of Nav2 in mice leads to cerebellar hypoplasia with abnormal foliation due to impaired axonal outgrowth. However, little is known about the involvement of the NAV2 gene in human disease phenotypes. In this study, we identified a female affected with neurodevelopmental impairment and a complex brain and cardiac malformations in which clinical exome sequencing led to the identification of NAV2 biallelic truncating variants. Through protein expression analysis and cell migration assay in patient-derived fibroblasts, we provide evidence linking NAV2 deficiency to cellular migration deficits. In model organisms, the overall CNS histopathology of the Nav2 hypomorphic mouse revealed developmental anomalies including cerebellar hypoplasia and dysplasia, corpus callosum hypo-dysgenesis, and agenesis of the olfactory bulbs. Lastly, we show that the NAV2 ortholog in Drosophila , sickie ( sick ) is widely expressed in the fly brain, and sick mutants are mostly lethal with surviving escapers showing neurobehavioral phenotypes. In summary, our results unveil a novel human neurodevelopmental disorder due to genetic loss of NAV2 , highlighting a critical conserved role of the NAV2 gene in brain and cerebellar development across species.

A Novel Stilbene Analogue: Antioxidant Activity and Application in Controlling the Quality and Bacterial Growth of Shrimp Refrigerated at 4ºC - Wei Xia; Vara Prasad Chakka; Kai Chen; Fan Wang; Yuan-Yuan Xie; Robert C. Hider; Tao Zhou (Journal of Aquatic Food Product Technology, 2022)

Older age, male sex, and cerebral microbleeds predict white matter loss after traumatic brain injury - David J. Robles; Ammar Dharani; Kenneth A. Rostowsky; Nikhil N. Chaudhari; Van Ngo; Fan Zhang; Lauren J. O’Donnell; Lauren Green; Nasim Sheikh-Bahaei; Helena C. Chui; Andrei Irimia (GeroScience, 2022)

Preface to the Special Issue: Climate Change and Variability of Tropical Cyclone Activity - Liguang Wu; Bin Wang; Johnny C. L. Chan; Kyung-Ja Ha; Il-Ju Moon; Jun Matsumoto; Zhemin Tan; Ke Fan (Advances in Atmospheric Sciences, 2022)

The impact of environmental pollution on the physical health of middle-aged and older adults in China - Hongli Fan; Yingcheng Wang; Ying Wang; Peter C. Coyte (Environmental Science and Pollution Research, 2022)

Challenges of anaerobic digestion in China - Q. Cheng; W. Huang; M. Jiang; C. Xu; G. Fan; J. Yan; B. Chai; Y. Zhang; Y. Zhang; S. Zhang; B. Xiao; G. Song (International Journal of Environmental Science and Technology, 2021)

The interaction of MYB, bHLH and WD40 transcription factors in red pear (Pyrus pyrifolia) peel - Daolei Cui; Shuxin Zhao; Huini Xu; Andrew C. Allan; Xiaodong Zhang; Lei Fan; Limei Chen; Jun Su; Quan Shu; Kunzhi Li (Plant Molecular Biology, 2021)

Flower strips adjacent to greenhouses help reduce pest populations and insecticide applications inside organic commercial greenhouses - Shu Li; Coline C. Jaworski; Séverin Hatt; Fan Zhang; Nicolas Desneux; Su Wang (Journal of Pest Science, 2021)

Damage zones induced by in situ stress unloading during excavation of diversion tunnels for the Jinping II hydropower project - Y. Fan; J. W. Zheng; X. Z. Cui; Z. D. Leng; F. Wang; C. C. Lv (Bulletin of Engineering Geology and the Environment, 2021)

Ore genesis and hydrothermal evolution of the Shaxi porphyry Cu–Au deposit, Anhui province, Eastern China: evidence from isotopes (S–Sr–H–O), pyrite, and fluid inclusions - Shiwei Wang; Taofa Zhou; Pete Hollings; Feng Yuan; Yu Fan; Noel C. White; Lejun Zhang (Mineralium Deposita, 2021)

Multiple generations of titanites and their geochemical characteristics record the magmatic-hydrothermal processes and timing of the Dongguashan porphyry-skarn Cu-Au system, Tongling district, Eastern China - Xin Xiao; Taofa Zhou; Noel C. White; Lejun Zhang; Yu Fan; Xuefeng Chen (Mineralium Deposita, 2021)

Adaptation of Willows in River Lowlands to Flooding under Arctic Amplification: Evidence from Nitrogen Content and Stable Isotope Dynamics - Rong Fan; Kei Tanekura; Tomoki Morozumi; Ryo Shingubara; Shunsuke Tei; Aleksandr Nogovitcyn; Egor Starostin; Trofim C. Maximov; Atsuko Sugimoto (Wetlands, 2020)

Polystoma luohetong n. sp. (Monogenea: Polystomatidae) from Rana chaochiaoensis Liu (Amphibia: Ranidae) in China - Lixian Fan; Weijiang Xu; Ting Jia; Edward C. Netherlands; Louis H. du Preez (Systematic Parasitology, 2020)

In Vitro Evaluation and Biodistribution Studies of HPMA Copolymers Targeting the Gastrin Releasing Peptide Receptor in Prostate Cancer - Sameer Alshehri; Wei Fan; Wenting Zhang; Jered C. Garrison (Pharmaceutical Research, 2020)

Suitable plant combinations for ecological floating beds in eutrophic subtropical coastal wetlands under different salinities: experimental evidences - J. C. Lyu; G. H. Lin; Z. Y. Fan; W. X. Lin; Z. Dai (International Journal of Environmental Science and Technology, 2020)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Transcription Factors Phox2a/2b Upregulate Expression of Noradrenergic and Dopaminergic Phenotypes in Aged Rat Brains - Yan Fan; Fei Zeng; Russell W. Brown; Jennifer B. Price; Thomas C. Jones; Meng-Yang Zhu (Neurotoxicity Research, 2020)

Longitudinal fMRI task reveals neural plasticity in default mode network with disrupted executive-default coupling and selective attention after traumatic brain injury - Shun-Chin Jim Wu; Lisanne M. Jenkins; Alexandra C. Apple; Julie Petersen; Furen Xiao; Lei Wang; Fan-pei Gloria Yang (Brain Imaging and Behavior, 2020)

“A reference genome assembly and adaptive trait analysis of Castanea mollissima ‘Vanuxem,’ a source of resistance to chestnut blight in restoration breeding” - Margaret Staton; Charles Addo-Quaye; Nathaniel Cannon; Jiali Yu; Tetyana Zhebentyayeva; Matthew Huff; Nurul Islam-Faridi; Shenghua Fan; Laura L. Georgi; C. Dana Nelson; Emily Bellis; Sara Fitzsimmons; et al. (Tree Genetics & Genomes, 2020)

Reductions in water, soil and nutrient losses and pesticide pollution in agroforestry practices: a review of evidence and processes - Xiai Zhu; Wenjie Liu; Jin Chen; L. Adrian Bruijnzeel; Zhun Mao; Xiaodong Yang; Rémi Cardinael; Fan-Rui Meng; Roy C. Sidle; Steffen Seitz; Vimala D. Nair; Kazuki Nanko; et al. (Plant and Soil, 2020)

Nitrogen deep placement mitigates methane emissions by regulating methanogens and methanotrophs in no-tillage paddy fields - D. J. Fan; T. Q. Liu; F. Sheng; S. H. Li; C. G. Cao; C. F. Li (Biology and Fertility of Soils, 2020)

High-gradient diffusion MRI reveals distinct estimates of axon diameter index within different white matter tracts in the in vivo human brain - Susie Y. Huang; Qiyuan Tian; Qiuyun Fan; Thomas Witzel; Barbara Wichtmann; Jennifer A. McNab; J. Daniel Bireley; Natalya Machado; Eric C. Klawiter; Choukri Mekkaoui; Lawrence L. Wald; Aapo Nummenmaa (Brain Structure and Function, 2020)

Provenance analysis of the Cretaceous Laiyang Group on Lingshan Island (western Yellow Sea, China) and its tectono-sedimentary implications - A. P. Fan; S. N. Sun; R. C. Yang; Z. Zhang; S. De; J. D. N. Nenzhelele; Y. Li; H. P. Liu; Y. Q. Zhou; J. Yuan (Australian Journal of Earth Sciences, 2020)

Targeting Two Antigens Associated with B-ALL with CD19-CD123 Compound Car T Cell Therapy - Lulu E. Yan; Hongyu Zhang; Masayuki Wada; Liu Fang; Jia Feng; Wenli Zhang; Qi Chen; Yuanzhen Cao; Kevin G. Pinz; Kevin H. Chen; Jessica C. Petrov; Xi Chen; et al. (Stem Cell Reviews and Reports, 2020)

Oplopanax elatus adventitious root production through fed-batch culture and their anti-bacterial effects - M. Y. Jin; X. C. Piao; X. H. Wu; M. Z. Fan; X. F. Li; C. R. Yin; M. L. Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Estimates of groundwater depletion under extreme drought in the Brazilian semi-arid region using GRACE satellite data: application for a small-scale aquifer - Maurício D. Melati; Ayan S. Fleischmann; Fernando M. Fan; Rodrigo C. D. Paiva; Gustavo B. Athayde (Hydrogeology Journal, 2019)

Coenzyme Q10 Alleviates Chronic Nucleoside Reverse Transcriptase Inhibitor-Induced Premature Endothelial Senescence - Yi-Fan Chen; Valeria Y. Hebert; Krisztian Stadler; Stephen Y. Xue; Kate Slaybaugh; Elliot Luttrell-Williams; Mitzi C. Glover; David M. Krzywanski; Tammy R. Dugas (Cardiovascular Toxicology, 2019)

Unpleasant Sound Elicits Negative Emotion and Reinstates Drug Seeking - Suchan Chang; Yu Fan; Joo Hyun Shin; Yeonhee Ryu; Mi Seon Kim; Scott C. Steffensen; Hyung Kyu Kim; Jin Mook Kim; Bong Hyo Lee; Eun Young Jang; Chae Ha Yang; Hee Young Kim (Molecular Neurobiology, 2019)

Geochemical characteristics of magnetite in Longqiao skarn iron deposit in the Middle-Lower Yangtze Metallogenic Belt, Eastern China - Yinan Liu; Yu Fan; Taofa Zhou; Xin Xiao; Noel C White; Jay Thompson; Haolan Hong; Lejun Zhang (Mineralium Deposita, 2019)

Revisiting the versatile buckwheat: reinvigorating genetic gains through integrated breeding and genomics approach - D. C. Joshi; Ganesh V. Chaudhari; Salej Sood; Lakshmi Kant; A. Pattanayak; Kaixuan Zhang; Yu Fan; Dagmar Janovská; Vladimir Meglič; Meiliang Zhou (Planta, 2019)

Floral isolation and pollination in two hummingbird-pollinated plants: the roles of exploitation barriers and pollinator competition - Ethan J. Temeles; Jia Liang; Molly C. Levy; Yong-Li Fan (Evolutionary Ecology, 2019)

Coring of Antarctic Subglacial Sediments - Da Gong; Xiaopeng Fan; Yazhou Li; Bing Li; Nan Zhang; Raphael Gromig; Emma C. Smith; Wolf Dummann; Sophie Berger; Olaf Eisen; Jan Tell; Boris K. Biskaborn; et al. (Journal of Marine Science and Engineering, 2019)
Coring sediments in subglacial aquatic environments offers unique opportunities for research on paleo-environments and paleo-climates because it can provide data from periods even earlier than ice cores, as well as the overlying ice histories, interactions between ice and the water system, life forms in extreme habitats, sedimentology, and stratigraphy. However, retrieving sediment cores from a subglacial environment faces more difficulties than sediment coring in oceans and lakes, resulting in low yields from the most current subglacial sediment coring methods. The coring tools should pass through a hot water-drilled access borehole, then the water column, to reach the sediment layers. The access boreholes are size-limited by the hot water drilling tools and techniques. These holes are drilled through ice up to 3000–4000 m thick, with diameters ranging from 10–60 cm, and with a refreezing closure rate of up to 6 mm/h after being drilled. Several purpose-built streamline corers have been developed to pass through access boreholes and collect the sediment core. The main coring objectives are as follows: (i) To obtain undisturbed water–sediment cores, either singly or as multi-cores and (ii) to obtain long cores with minimal stratigraphic deformation. Subglacial sediment coring methods use similar tools to those used in lake and ocean coring. These methods include the following: Gravity coring, push coring, piston coring, hammer or percussion coring, vibrocoring, and composite methods. Several core length records have been attained by different coring methods, including a 290 cm percussion core from the sub-ice-shelf seafloor, a 400 cm piston core from the sub-ice-stream, and a 170 cm gravity core from a subglacial lake. There are also several undisturbed water–sediment cores that have been obtained by gravity corers or hammer corers. Most current coring tools are deployed by winch and cable facilities on the ice surface. There are three main limitations for obtaining long sediment cores which determines coring tool development, as follows: Hot-water borehole radial size restriction, the sedimentary structure, and the coring techniques. In this paper, we provide a general view on current developments in coring tools, including the working principles, corer characteristics, operational methods, coring site locations, field conditions, coring results, and possible technical improvements. Future prospects in corer design and development are also discussed.

Adjunctive telmisartan treatment on body metabolism in clozapine or olanzapine treated patients with schizophrenia: a randomized, double blind, placebo controlled trial - Xiaoduo Fan; Paul Copeland; Shukair Nawras; Amy Harrington; Oliver Freudenreich; Donald C. Goff; David C. Henderson (Psychopharmacology, 2019)

Seasonal climatic effects and feedbacks of anthropogenic heat release due to global energy consumption with CAM5 - Bing Chen; C. Wu; X. Liu; L. Chen; Jian Wu; H. Yang; Tao Luo; Xue Wu; Yiquan Jiang; Lei Jiang; H. Y. Brown; Z. Lu; et al. (Climate Dynamics, 2019)

Response and Recovery of Low-Salinity Marsh Plant Communities to Presses and Pulses of Elevated Salinity - Fan Li; Steven C. Pennings (Estuaries and Coasts, 2019)

Spatio-temporal evolution of mass wasting after the 2008 Mw 7.9 Wenchuan earthquake revealed by a detailed multi-temporal inventory - Xuanmei Fan; Guillem Domènech; Gianvito Scaringi; Runqiu Huang; Qiang Xu; Tristram C. Hales; Lanxin Dai; Qin Yang; Oliver Francis (Landslides, 2018)

The primate extinction crisis in China: immediate challenges and a way forward - Baoguo Li; Ming Li; Jinhua Li; Pengfei Fan; Qingyong Ni; Jiqi Lu; Xuming Zhou; Yongcheng Long; Zhigang Jiang; Peng Zhang; Zhipang Huang; Chenming Huang; et al. (Biodiversity and Conservation, 2018)

Assessing environmental impacts and change in Myanmar's mangrove ecosystem service value due to deforestation (2000–2014) - Ronald C. Estoque; Soe W. Myint; Chuyuan Wang; Asif Ishtiaque; Toe T. Aung; Lucy Emerton; Makoto Ooba; Yasuaki Hijioka; Myat S. Mon; Zhe Wang; Chao Fan (Global Change Biology, 2018)
Myanmar is one of the mangrove‐richest countries in the world, providing valuable ecosystem services to people. However, due to deforestation driven primarily by agricultural expansion, Myanmar's mangrove forest cover has declined dramatically over the past few decades, while what remains is still under pressure. To support management planning, accurate quantification of mangrove forest cover changes on a national scale is needed. In this study, we quantified Myanmar's mangrove forest cover changes between 2000 and 2014 using remotely sensed data, examined the environmental impacts of such changes, and estimated the changes in the economic values of mangrove ecosystem services in the country. Results indicate that Myanmar had a net mangrove loss of 191,122 ha over the study period. Since 2000, Myanmar has been losing mangrove forest cover at an alarming rate of 14,619 ha/year (2.2%/year). The loss was predominant in Rakhine and Ayeyarwady. The observed mangrove forest cover loss has resulted in decreased evapotranspiration, carbon stock, and tree cover percentage. Due to deforestation, Myanmar also suffered a net loss of 2,397 million US $/year in its mangrove ecosystem service value (i.e. 28.7% decrease from 2000), in which maintenance of fisheries nursery populations and habitat and coastal protection were among those services that were greatly affected. We suggest that intensive reforestation and mangrove protection programs be implemented immediately. Agroforestry and community forestry programs are encouraged in areas that are under immense pressure from paddy field expansion, fuelwood extraction, charcoal production, and fish and shrimp farming activities. Potential alternative sustainable solutions should include intensive government‐led private forest plantations or community‐owned forest plantations to be developed with care by local farmers, nongovernmental organizations, and business owners.

Responses of Tidal Freshwater and Brackish Marsh Macrophytes to Pulses of Saline Water Simulating Sea Level Rise and Reduced Discharge - Fan Li; Steven C. Pennings (Wetlands, 2018)

Ras-Related C3 Botulinum Toxin Substrate 1 Promotes Axonal Regeneration after Stroke in Mice - Lin Liu; Hui Yuan; Yanhua Yi; Edward C. Koellhoffer; Yashasvee Munshi; Fan Bu; Yi Zhang; Zhenggang Zhang; Louise D. McCullough; Jun Li (Translational Stroke Research, 2018)

Occurrence characteristics and controls over mobile fluids in a tight sandstone reservoir - Q. Q. Dai; G. W. Wang; C. J. Lu; Y. Z. Zhang; Z. L. Zhou; X. Q. Fan; S. Wang; Z. B. He (Australian Journal of Earth Sciences, 2018)

Intermittent micro-aeration control of methane emissions from an integrated vertical-flow constructed wetland during agricultural domestic wastewater treatment - Xiaoling Liu; Ke Zhang; Liangqian Fan; Hongbing Luo; Mingshu Jiang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Guozhu He; Jingting Wang; Aiping Pu (Environmental Science and Pollution Research, 2018)

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Glucohexaose-induced protein phosphatase 2C regulates cell redox status of cucumber seedling - Q M Chen; Y Yu; C M Lin; N Cui; J Y Zhao; T F Song; H Y Fan (Journal of Biosciences, 2018)

Differential expression of hormone related genes between extreme segregants of a Saccharum interspecific F2 population - Fan Zhu; Ching Man Wai; Jisen Zhang; Tyler C. Jones; Chifumi Nagai; Ray Ming (Euphytica, 2018)

The China Plant Trait Database: toward a comprehensive regional compilation of functional traits for land plants - Han Wang; Sandy P. Harrison; Iain C. Prentice; Yanzheng Yang; Fan Bai; Henrique F. Togashi; Meng Wang; Shuangxi Zhou; Jian Ni (Ecology, 2018)
Plant functional traits provide information about adaptations to climate and environmental conditions, and can be used to explore the existence of alternative plant strategies within ecosystems. Trait data are also increasingly being used to provide parameter estimates for vegetation models. Here we present a new database of plant functional traits from China. Most global climate and vegetation types can be found in China, and thus the database is relevant for global modeling. The China Plant Trait Database contains information on morphometric, physical, chemical, and photosynthetic traits from 122 sites spanning the range from boreal to tropical, and from deserts and steppes through woodlands and forests, including montane vegetation. Data collection at each site was based either on sampling the dominant species or on a stratified sampling of each ecosystem layer. The database contains information on 1,215 unique species, though many species have been sampled at multiple sites. The original field identifications have been taxonomically standardized to the Flora of China. Similarly, derived photosynthetic traits, such as electron‐transport and carboxylation capacities, were calculated using a standardized method. To facilitate trait–environment analyses, the database also contains detailed climate and vegetation information for each site. The data set is released under a Creative Commons BY license. When using the data set, we kindly request that you cite this article, recognizing the hard work that went into collecting the data and the authors' willingness to make it publicly available.

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Close association between intestinal microbiota and irritable bowel syndrome - W.-T. Fan; C. Ding; N.-N. Xu; S. Zong; P. Ma; B. Gu (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Tree species richness in northeastern China: geographical variation and minimum areas - X. H. Fan; H. J. He; J. Wang; C. Y. Xu; K. v. Gadow (Community Ecology, 2017)

Strategy for CYP3A Induction Risk Assessment from Preclinical Signal to Human: a Case Example of a Late-Stage Discovery Compound - Jialin Mao; Peter Fan; Susan Wong; Jianshuang Wang; Moulay Hicham Alaoui Ismaili; Brian Dean; Cornelis E. C. A. Hop; Matthew Wright; Yuan Chen (Pharmaceutical Research, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Isolation, identification and pathogenicity of Vibrio harveyi , the causal agent of skin ulcer disease in juvenile hybrid groupers Epinephelus fuscoguttatus × Epinephelus lanceolatus - G M Shen; C Y Shi; C Fan; D Jia; S Q Wang; G S Xie; G Y Li; Z L Mo; J Huang (Journal of Fish Diseases, 2017)
The hybrid grouper, Epinephelus fuscoguttatus (♀) × Epinephelus lanceolatus (♂), is a newly bred cultivated marine fish species of high economic value. However, a skin ulcer disease with high mortality has occurred, and the responsible pathogen remains unknown. In this study, we summarized the epidemic status and external signs of this disease. We screened potential pathogens and finally isolated one bacterial strain ML 01 from affected fish. We subjected healthy juvenile hybrid groupers to bacterial challenge tests with the isolate by immersion, immersion after dermal abrasion and intraperitoneal injection, respectively. Within 14 days post‐infection, the isolate ML 01 caused mass mortality of juveniles infected via immersion after dermal abrasion or intraperitoneal injection. Diseased juveniles displayed obvious signs of skin ulcers. The median lethal dose of ML 01 by intraperitoneal injection was 1.10 × 10 5 colony‐forming units. ML 01 was identified as Vibrio harveyi by bacterial morphology, analytical profile index identification, 16S rDNA sequencing and multilocus sequence analysis. Antibiotic susceptibility tests showed that ML 01 was sensitive to ceftriaxone, doxycycline and minocycline. The results of this study suggest that V. harveyi is the causal agent of skin ulcer disease in juvenile hybrid groupers, thus providing a basis for effective control and prevention of this disease.

Involvement of methylated HBHA expressed from Mycobacterium smegmatis in an IFN-γ release assay to aid discrimination between latent infection and active tuberculosis in BCG-vaccinated populations - H.-L. Wen; C.-L. Li; G. Li; Y.-H. Lu; H.-C. Li; T. Li; H.-M. Zhao; K. Wu; D. B. Lowrie; J.-X. Lv; S.-H. Lu; X.-Y. Fan (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Real-time monitoring instrument designed for the deformation and sliding period of colluvial landslides - Y. B. Fan; S. W. Yang; L. K. Xu; S. H. Li; C. Feng; B. F. Liang (Bulletin of Engineering Geology and the Environment, 2017)

Exponential leap-forward gradient scheme for determining the isothermal layer depth from profile data - Peter C. Chu; Chenwu Fan (Journal of Oceanography, 2017)

Haplotype diversity of mtCOI in the fall webworm Hyphantria cunea (Lepidoptera: Arctiidae) in introduced regions in China, Iran, Japan, Korea, and its homeland, the United States - Fan Yang; Jalal Jalali Sendi; R. C. Johns; Makio Takeda (Applied Entomology and Zoology, 2017)

Exome sequence genotype imputation in globally diverse hexaploid wheat accessions - Fan Shi; Josquin Tibbits; Raj K. Pasam; Pippa Kay; Debbie Wong; Joanna Petkowski; Kerrie L. Forrest; Ben J. Hayes; Alina Akhunova; John Davies; Steven Webb; German C. Spangenberg; et al. (Theoretical and Applied Genetics, 2017)

Copy-number variant analysis of classic heterotaxy highlights the importance of body patterning pathways - Erin M. Hagen; Robert J. Sicko; Denise M. Kay; Shannon L. Rigler; Aggeliki Dimopoulos; Shabbir Ahmad; Margaret H. Doleman; Ruzong Fan; Paul A. Romitti; Marilyn L. Browne; Michele Caggana; Lawrence C. Brody; et al. (Human Genetics, 2016)

137Cs tracing dynamics of soil erosion, organic carbon, and total nitrogen in terraced fields and forestland in the Middle Mountains of Nepal - Zheng-an Su; Dong-hong Xiong; Wei Deng; Yi-fan Dong; Jing Ma; C Poudel Padma; B Sher Gurung (Journal of Mountain Science, 2016)

Osteogenic Treatment Initiating a Tissue-Engineered Cartilage Template Hypertrophic Transition - J. Y. Fu; S. Y. Lim; P. F. He; C. J. Fan; D. A. Wang (Annals of Biomedical Engineering, 2016)

Projecting In-stream Dissolved Organic Carbon and Total Mercury Concentrations in Small Watersheds Following Forest Growth and Clearcutting - Chengfu Zhang; Rob C. Jamieson; Fan-Rui Meng; Robert Gordon; Charles P.-A. Bourque (Water, Air, & Soil Pollution, 2016)

Ocean spectral data assimilation without background error covariance matrix - Peter C. Chu; Chenwu Fan; Tetyana Margolina (Ocean Dynamics, 2016)

Cytosolic localization of Fox proteins in motor neurons of G93A SOD1 mice - Xiaoxing Ma; Patrick C. Turnbull; Eli Prentice Crapper; Henan Wang; Anna Drannik; Fan Jiang; Sean Xia; John Turnbull (Histochemistry and Cell Biology, 2016)

Age at cancer diagnosis, amenability to medical interventions, and racial/ethnic disparities in cancer mortality - Parisa Tehranifar; Abhishek Goyal; Jo C. Phelan; Bruce G. Link; Yuyan Liao; Xiaozhou Fan; Manisha Desai; Mary Beth Terry (Cancer Causes & Control, 2016)

Erratum to: Jasmonic Acid Mediates Tomato’s Response to Root Knot Nematodes - J. W. Fan; C. L. Hu; L. N. Zhang; Z. L. Li; F. K. Zhao; S. H. Wang (Journal of Plant Growth Regulation, 2016)

Reorganization and expansion of the nidoviral family Arteriviridae - Jens H. Kuhn; Michael Lauck; Adam L. Bailey; Alexey M. Shchetinin; Tatyana V. Vishnevskaya; Yīmíng Bào; Terry Fei Fan Ng; Matthew LeBreton; Bradley S. Schneider; Amethyst Gillis; Ubald Tamoufe; Joseph Le Doux Diffo; et al. (Archives of Virology, 2016)

The role of salinity in seed maturation of the euhalophyte Suaeda salsa - J. C. Zhou; T. T. Fu; N. Sui; J. R. Guo; G. Feng; J. L. Fan; J. Song (Plant Biosystems, 2016)

Efficacy of oral moxifloxacin for aerobic vaginitis - C. Wang; C. Han; N. Geng; A. Fan; Y. Wang; Y. Yue; H. Zhang; F. Xue (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

A Real-Time Analysis and Feedback System for Quality Control of Dam Foundation Grouting Engineering - D. H. Zhong; F. G. Yan; M. C. Li; C. X. Huang; K. Fan; J. F. Tang (Rock Mechanics and Rock Engineering, 2015)

Mutations of the SLIT2–ROBO2 pathway genes SLIT2 and SRGAP1 confer risk for congenital anomalies of the kidney and urinary tract - Daw-Yang Hwang; Stefan Kohl; Xueping Fan; Asaf Vivante; Stefanie Chan; Gabriel C. Dworschak; Julian Schulz; Albertien M. van Eerde; Alina C. Hilger; Heon Yung Gee; Tracie Pennimpede; Bernhard G. Herrmann; et al. (Human Genetics, 2015)

Genetics of skin color variation in Europeans: genome-wide association studies with functional follow-up - Fan Liu; Mijke Visser; David L. Duffy; Pirro G. Hysi; Leonie C. Jacobs; Oscar Lao; Kaiyin Zhong; Susan Walsh; Lakshmi Chaitanya; Andreas Wollstein; Gu Zhu; Grant W. Montgomery; et al. (Human Genetics, 2015)

The juxtamembrane sequence of the Hepatitis C virus polymerase can affect RNA synthesis and inhibition by allosteric polymerase inhibitors - Y. Wen; X. Lin; B. Fan; C. T. Ranjith-Kumar; C. C. Kao (Virus Genes, 2015)

Changes in root morphology and physiology to limited phosphorus and moisture in a locally-selected cultivar and an introduced cultivar of Medicago sativa L. growing in alkaline soil - Jing-Wei Fan; Yan-Lei Du; Neil C. Turner; Bing-Ru Wang; Yan Fang; Yue Xi; Xiao-Ran Guo; Feng-Min Li (Plant and Soil, 2015)

Synthesis of agar-stabilized nanoscale zero-valent iron particles and removal study of hexavalent chromium - C. Jiao; Y. Cheng; W. Fan; J. Li (International Journal of Environmental Science and Technology, 2015)

Jasmonic Acid Mediates Tomato’s Response to Root Knot Nematodes - J. W. Fan; C. L. Hu; L. N. Zhang; Z. L. Li; F. K. Zhao; S. H. Wang (Journal of Plant Growth Regulation, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

An auto-flocculation strategy for Chlorella vulgaris - Y. Shen; Z. Fan; C. Chen; X. Xu (Biotechnology Letters, 2015)

Decreased BMP2 signal in GIT1 knockout mice slows bone healing - T. J. Sheu; Wei Zhou; Jin Fan; Hao Zhou; Michael J. Zuscik; Chao Xie; Guoyong Yin; Bradford C. Berk (Molecular and Cellular Biochemistry, 2014)

SLDP: a Novel Protein Related to Caleosin Is Associated with the Endosymbiotic Symbiodinium Lipid Droplets from Euphyllia glabrescens - Buntora Pasaribu; I-Ping Lin; Jason T. C. Tzen; Guang-Yuh Jauh; Tung-Yung Fan; Yu-Min Ju; Jing-O Cheng; Chii-Shiarng Chen; Pei-Luen Jiang (Marine Biotechnology, 2014)

Identification of the microRNA Expression Profile in the Regenerative Neonatal Mouse Heart by Deep Sequencing - H. L. Liu; J. G. Zhu; Y. Q. Liu; Z. G. Fan; C. Zhu; L. M. Qian (Cell Biochemistry and Biophysics, 2014)

The role of cotyledons in the establishment of Suaeda physophora seedlings - J. C. Zhou; W. W. Zhao; C. H. Yin; J. Song; B. S. Wang; J. L. Fan; G. Feng (Plant Biosystems, 2014)

Stability analyses and numerical simulations of the single degree of freedom spring-slider system obeying the revised rate- and state-dependent friction law - Q. Fan; C. Xu; J. Niu; G. Jiang; Y. Liu (Journal of Seismology, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Ocean acidification has no effect on thermal bleaching in the coral Seriatopora caliendrum - C. B. Wall; T.-Y. Fan; P. J. Edmunds (Coral Reefs, 2014)

Neck cooling and cognitive performance following exercise-induced hyperthermia - Jason K. W. Lee; Aldrich C. H. Koh; Serene X. T. Koh; Glen J. X. Liu; Amanda Q. X. Nio; Priscilla W. P. Fan (European Journal of Applied Physiology, 2014)

Endothelial-like properties of claudin-low breast cancer cells promote tumor vascular permeability and metastasis - J. Chuck Harrell; Adam D. Pfefferle; Nicole Zalles; Aleix Prat; Cheng Fan; Andrey Khramtsov; Olufunmilayo I. Olopade; Melissa A. Troester; Andrew C. Dudley; Charles M. Perou (Clinical & Experimental Metastasis, 2014)

Hydrated mucilage reduces post-dispersal seed removal of a sand desert shrub by ants in a semiarid ecosystem - Xuejun Yang; Carol C. Baskin; Jerry M. Baskin; Ruiru Gao; Fan Yang; Lingling Wei; Leilei Li; Hongju He; Zhenying Huang (Oecologia, 2013)

Physiological acclimation to elevated temperature in a reef-building coral from an upwelling environment - A. B. Mayfield; T.-Y. Fan; C.-S. Chen (Coral Reefs, 2013)

Figured grain in aspen is heritable and not affected by graft-transmissible signals - Youran Fan; Kendal Rupert; Alex C. Wiedenhoeft; Keith Woeste; Christian Lexer; Richard Meilan (Trees, 2013)

Genetic differ in TLR4 gene polymorphisms and expression involved in Salmonella natural and artificial infection respectively in Chinese native chicken breeds - H. F. Li; Y. Hu; H. Hu; C. Song; J. T. Shu; C. H. Zhu; S. J. Zhang; J. H. Fan; W. W. Chen (Molecular Biology Reports, 2013)

The physiological and molecular responses of larvae from the reef-building coral Pocillopora damicornis exposed to near-future increases in temperature and pCO2 - H. M. Putnam; A. B. Mayfield; T. Y. Fan; C. S. Chen; R. D. Gates (Marine Biology, 2013)

The evolutionary history of X iphophorus fish and their sexually selected sword: a genome‐wide approach using restriction site‐associated DNA sequencing - Julia C. Jones; Shaohua Fan; Paolo Franchini; Manfred Schartl; Axel Meyer (Molecular Ecology, 2013)
Next‐generation sequencing ( NGS ) techniques are now key tools in the detection of population genomic and gene expression differences in a large array of organisms. However, so far few studies have utilized such data for phylogenetic estimations. Here, we use NGS data obtained from genome‐wide restriction site‐associated DNA ( RAD ) (∼66000 SNPs) to estimate the phylogenetic relationships among all 26 species of swordtail and platyfish (genus X iphophorus ) from C entral A merica. Past studies, both sequence and morphology‐based, have differed in their inferences of the evolutionary relationships within this genus, particularly at the species‐level and among monophyletic groupings. We show that using a large number of markers throughout the genome, we are able to infer the phylogenetic relationships with unparalleled resolution for this genus. The relationships among all three major clades and species within each of them are highly resolved and consistent under maximum likelihood, B ayesian inference and maximum parsimony. However, we also highlight the current cautions with this data type and analyses. This genus exhibits a particularly interesting evolutionary history where at least two species may have arisen through hybridization events. Here, we are able to infer the paternal lineages of these putative hybrid species. Using the RAD ‐marker‐based tree we reconstruct the evolutionary history of the sexually selected sword trait and show that it may have been present in the common ancestor of the genus. Together our results highlight the outstanding capacity that RAD sequencing data has for resolving previously problematic phylogenetic relationships, particularly among relatively closely related species.

High-resolution profiles of iron, manganese, cobalt, cadmium, copper and zinc in the pore water of estuarine sediment - Z. Yang; W. Guo; Y. Fan; C. Lin; M. He (International Journal of Environmental Science and Technology, 2013)

Comprehensive candidate gene study highlights UGT1A and BNC2 as new genes determining continuous skin color variation in Europeans - Leonie C. Jacobs; Andreas Wollstein; Oscar Lao; Albert Hofman; Caroline C. Klaver; André G. Uitterlinden; Tamar Nijsten; Manfred Kayser; Fan Liu (Human Genetics, 2013)

Speleothem evidence for temporal–spatial variation in the East Asian Summer Monsoon since the Medieval Warm Period - Peter C. Chu; Hong‐Chun Li; Chenwu Fan; Yong‐Heng Chen (Journal of Quaternary Science, 2012)
Published annual‐to‐decadal‐resolution stalagmite δ 18 O records since AD 900 from six caves (Dongge, Furong, Heshang, Buddha, Shihua and Wanxiang) in China were analyzed to detect temporal and spatial variability of the East Asian Summer Monsoon strength, which strongly affects wet/dry conditions in eastern China. The empirical mode decomposition method was used to obtain trends of the six cave records. After the base trend was determined, δ 18 O anomalies of each record were computed by subtracting the base trend. Mean δ 18 O anomaly values of the detrended time series for each cave record were calculated for four periods: (i) Medieval Warm Period (MWP; AD 900–1250): (ii) Little Ice Age phase 1 (LIA‐1; AD 1250–1550); (iii) Little Ice Age phase 2 (LIA‐2; AD 1550–1850); and (iv) modern period (MD; AD 1850–2000). From these anomalies, the temporal and spatial variability of wet/dry conditions has been identified. Positive values of the mean δ 18 O anomalies indicating drier conditions appeared in the lower Yangtze River Drainage Area and Southeast Coast Area during MD‐1, LIA‐1 and MWP, whereas negative values existed in north, south and Yangtze areas of eastern China during LIA‐2. The results agree with the dryness/wetness index reconstructed by Chinese historic records in general. These results illustrate that wet and dry conditions in different regions of eastern China could be opposite under monsoon influence, so that no single speleothem δ 18 O record could represent the monsoonal climate in this vast region. Climatic patterns in the monsoonal region can be either a combination of warm/wet and cold/dry or a combination of cold/wet and warm/dry on annual‐to‐centennial scales. A 128‐year periodic cycle exists in all six cave records, whereas 64‐year (possibly a harmonic of 128‐year periodicity) and 42‐year periodicities appear in Shihua, Heshang and Dongge records. These cycles may reflect the influence of solar activity on the East Asian Summer Monsoon. Copyright © 2012 John Wiley & Sons, Ltd.

Assessment of the genetic diversity in a collection of Erianthus arundinaceus - Q. Cai; K. S. Aitken; Y. H. Fan; G. Piperidis; X. L. Liu; C. L. McIntyre; X. Q. Huang; P. Jackson (Genetic Resources and Crop Evolution, 2012)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Investigation of the application of Acadian Marine Plant Extract Powder (AMPEP) to enhance the growth, phenolic content, free radical scavenging, and iron chelating activities of Kappaphycus Doty (Solieriaceae, Gigartinales, Rhodophyta) - Anicia Q. Hurtado; Munib Joe; Roman C. Sanares; Di Fan; Balakrishnan Prithiviraj; Alan T. Critchley (Journal of Applied Phycology, 2012)

Canine models of Duchenne muscular dystrophy and their use in therapeutic strategies - Joe N. Kornegay; Janet R. Bogan; Daniel J. Bogan; Martin K. Childers; Juan Li; Peter Nghiem; David A. Detwiler; C. Aaron Larsen; Robert W. Grange; Ratna K. Bhavaraju-Sanka; Sandra Tou; Bruce P. Keene; et al. (Mammalian Genome, 2012)

Missense substitutions in the GAS1 protein present in holoprosencephaly patients reduce the affinity for its ligand, SHH - Daniel E. Pineda-Alvarez; Erich Roessler; Ping Hu; Kshitij Srivastava; Benjamin D. Solomon; C. Evan Siple; Chen-Ming Fan; Maximilian Muenke (Human Genetics, 2012)

Extraction of spatial-temporal rules from mesoscale eddies in the South China Sea based on rough set theory - Y. Du; X. Fan; Z. He; F. Su; C. Zhou; H. Mao; D. Wang (Ocean Science, 2011)
In this paper, a rough set theory is introduced to represent spatial-temporal relationships and extract the corresponding rules from typical mesoscale-eddy states in the South China Sea (SCS). Three decision attributes are adopted in this study, which make the approach flexible in retrieving spatial-temporal rules with different features. The results demonstrate that this approach is effective, and therefore provides a powerful approach to forecasts in the future studies. Spatial-temporal rules in the SCS indicate that warm eddies following the rules are generally in the southeastern and central SCS around 2000 m isobaths in winter. Their intensity and vorticity are weaker than those of cold eddies. They usually move a shorter distance. By contrast, cold eddies are in 2000 m and deeper regions of the southwestern and northeastern SCS in spring and fall. Their intensity and vorticity are strong. Usually they move a long distance. In winter, a few rules are followed by cold eddies in the northern tip of the basin and southwest of Taiwan Island rather than warm eddies, indicating cold eddies may be well-regulated in the region. Several warm-eddy rules are achieved west of Luzon Island, indicating warm eddies may be well-regulated in the region as well. Otherwise, warm and cold eddies are distributed not only in the jet flow off southern Vietnam induced by intraseasonal wind stress in summer-fall, but also in the northern shallow water, which should be a focus of a future study.

Eight paths of ERK1/2 signalling pathway regulating hepatocyte proliferation in rat liver regeneration - J. W. LI; G. P. WANG; J. Y. FAN; C. F. CHANG; C. S. XU (Journal of Genetics, 2011)

Influence of indomethacin on the ventilatory and cerebrovascular responsiveness to hypoxia - Jui-Lin Fan; Keith R. Burgess; Kate N. Thomas; Karen C. Peebles; Samuel J. E. Lucas; Rebekah A. I. Lucas; James D. Cotter; Philip N. Ainslie (European Journal of Applied Physiology, 2011)

Maximum angle method for determining mixed layer depth from seaglider data - Peter C. Chu; Chenwu Fan (Journal of Oceanography, 2011)

Hexachlorocyclohexane (HCH) as new Stockholm Convention POPs—a global perspective on the management of Lindane and its waste isomers - John Vijgen; P. C. Abhilash; Yi Fan Li; Rup Lal; Martin Forter; Joao Torres; Nandita Singh; Mohammad Yunus; Chongguo Tian; Andreas Schäffer; Roland Weber (Environmental Science and Pollution Research, 2011)

Transcriptome atlas of eight liver cell types uncovers effects of histidine catabolites on rat liver regeneration - C. F. Chang; J. Y. Fan; F. C. Zhang; J. Ma; C. S. Xu (Journal of Genetics, 2010)

An Efficient Modeling Approach to Simulate Heat Transfer Rate between Fracture and Matrix Regions for Oil Shale Retorting - Fan Zhang; Jack C. Parker (Transport in Porous Media, 2010)

Simultaneous declines in radon and methane precursory to 2008 M W 5.0 Antung earthquake: corroboration of in-situ volatilization - T. Kuo; W. Cheng; C. Lin; K. Fan; G. Chang; T. Yang (Natural Hazards, 2010)

Estimation of aseismic crustal-strain using radon precursors of the 2003 M 6.8, 2006 M 6.1, and 2008 M 5.0 earthquakes in eastern Taiwan - T. Kuo; C. Lin; G. Chang; K. Fan; W. Cheng; C. Lewis (Natural Hazards, 2010)

Skin cooling aids cerebrovascular function more effectively under severe than moderate heat stress - Rebekah A. I. Lucas; Philip N. Ainslie; Jui-Lin Fan; Luke C. Wilson; Kate N. Thomas; James D. Cotter (European Journal of Applied Physiology, 2010)

The Effect of Intermittent Static Biaxial Tensile Strains on Tissue Engineered Cartilage - Jackie C. Y. Fan; Stephen D. Waldman (Annals of Biomedical Engineering, 2010)

Rapid evolution and selection inferred from the transcriptomes of sympatric crater lake cichlid fishes - K. R. ELMER; S. FAN; H. M. GUNTER; J. C. JONES; S. BOEKHOFF; S. KURAKU; A. MEYER (Molecular Ecology, 2010)
Crater lakes provide a natural laboratory to study speciation of cichlid fishes by ecological divergence. Up to now, there has been a dearth of transcriptomic and genomic information that would aid in understanding the molecular basis of the phenotypic differentiation between young species. We used next‐generation sequencing (Roche 454 massively parallel pyrosequencing) to characterize the diversity of expressed sequence tags between ecologically divergent, endemic and sympatric species of cichlid fishes from crater lake Apoyo, Nicaragua: benthic Amphilophus astorquii and limnetic Amphilophus zaliosus . We obtained 24 174 A. astorquii and 21 382 A. zaliosus high‐quality expressed sequence tag contigs, of which 13 106 pairs are orthologous between species. Based on the ratio of nonsynonymous to synonymous substitutions, we identified six sequences exhibiting signals of strong diversifying selection ( K a / K s > 1). These included genes involved in biosynthesis, metabolic processes and development. This transcriptome sequence variation may be reflective of natural selection acting on the genomes of these young, sympatric sister species. Based on K s ratios and p‐distances between 3′‐untranslated regions (UTRs) calibrated to previously published species divergence times, we estimated a neutral transcriptome‐wide substitutional mutation rate of ∼1.25 × 10 −6 per site per year. We conclude that next‐generation sequencing technologies allow us to infer natural selection acting to diversify the genomes of young species, such as crater lake cichlids, with much greater scope than previously possible.

Parathyroid Hormone PTH(1-34) Formulation that Enables Uniform Coating on a Novel Transdermal Microprojection Delivery System - Mahmoud Ameri; Shelley C. Fan; Yuh-Fun Maa (Pharmaceutical Research, 2010)

Cloning, chromosomal localization, SNP detection and association analysis of the porcine IRS-1 gene - P.-X. Niu; Z. Huang; C.-C. Li; B. Fan; K. Li; B. Liu; M. Yu; S.-H. Zhao (Molecular Biology Reports, 2009)

Fibulin-1 and fibrinogen in human atherosclerotic lesions - W. Scott Argraves; Asashi Tanaka; Elizabeth P. Smith; Waleed O. Twal; Kelley M. Argraves; Daping Fan; Christian C. Haudenschild (Histochemistry and Cell Biology, 2009)

Are Hylobates lar Extirpated from China? - Cyril C. Grueter; Xuelong Jiang; Roger Konrad; Pengfei Fan; Zhenhua Guan; Thomas Geissmann (International Journal of Primatology, 2009)

An Automated Pipeline for Dendrite Spine Detection and Tracking of 3D Optical Microscopy Neuron Images of In Vivo Mouse Models - Jing Fan; Xiaobo Zhou; Jennifer G. Dy; Yong Zhang; Stephen T. C. Wong (Neuroinformatics, 2009)

Investigation of Lpin1 as a candidate gene for fat deposition in pigs - X. P. He; X. W. Xu; S. H. Zhao; B. Fan; M. Yu; M. J. Zhu; C. C. Li; Z. Z. Peng; B. Liu (Molecular Biology Reports, 2009)

Temperature-dependent Activation of Neurons by Continuous Near-infrared Laser - Shanshan Liang; Fan Yang; Cheng Zhou; Yue Wang; Shao Li; C. K. Sun; Jose Luis Puglisi; Donald Bers; Changsen Sun; Jie Zheng (Cell Biochemistry and Biophysics, 2009)

The MSX1 allele 4 homozygous child exposed to smoking at periconception is most sensitive in developing nonsyndromic orofacial clefts - Marie-José H. van den Boogaard; Dominique de Costa; Ingrid P. C. Krapels; Fan Liu; Cock van Duijn; Richard J. Sinke; Dick Lindhout; Régine P. M. Steegers-Theunissen (Human Genetics, 2008)

Morphological and physiological variation in western redcedar (Thuja plicata) populations under contrasting soil water conditions - Shihe Fan; Steven C. Grossnickle; John H. Russell (Trees, 2008)

Transgenic maize plants expressing a fungal phytase gene - Rumei Chen; Guangxing Xue; Ping Chen; Bin Yao; Wenzhu Yang; Qianli Ma; Yunliu Fan; Zuoyu Zhao; Mitchell C. Tarczynski; Jinrui Shi (Transgenic Research, 2008)

The genomic sequence and biological properties of Pennisetum mosaic virus, a novel monocot-infecting potyvirus - C. L. Deng; W. J. Wang; Z. Y. Wang; X. Jiang; Y. Y. Cao; T. Zhou; F. R. Wang; H. F. Li; Z. F. Fan (Archives of Virology, 2008)

Acid Volatile Sulfides and Simultaneously Extracted Metals in a Metal-Polluted Area of Taihu Lake, China - H. B. Yin; C. X. Fan; S. M. Ding; L. Zhang; B. Li (Bulletin of Environmental Contamination and Toxicology, 2008)

Short-term carbon dioxide emissions and denitrification losses from soils amended with low-P manure from genetically modified pigs - X. M. Yang; C. F. Drury; T. Q. Zhang; A. Ajakaiye; C. W. Forsberg; M. Z. Fan; J. P. Philip (Nutrient Cycling in Agroecosystems, 2008)

Paired cloning vectors for complementation of mutations in the cyanobacterium Anabaena sp. strain PCC 7120 - C. Peter Wolk; Qing Fan; Ruanbao Zhou; Guocun Huang; Sigal Lechno-Yossef; Tanya Kuritz; Elizabeth Wojciuch (Archives of Microbiology, 2007)

Characterization of intergeneric hybrids of Erianthus rockii and Saccharum using molecular markers - K. Aitken; J. Li; L. Wang; C. Qing; Y. H. Fan; P. Jackson (Genetic Resources and Crop Evolution, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Comparison of four infectious bursal disease viruses isolated from different bird species - Y. S. Wang; Z. C. Wang; Y. D. Tang; Z. L. Shi; K. W. He; Y. Li; J. B. Hou; H. C. Yao; H. J. Fan; C. P. Lu (Archives of Virology, 2007)

Determination of carryover and contamination for mass spectrometry-based chromatographic assays - Nicola C. Hughes; Ernest Y. K. Wong; Juan Fan; Navgeet Bajaj (The AAPS Journal, 2007)

High-density single nucleotide polymorphism array analysis in patients with germline deletions of 22q11.2 and malignant rhabdoid tumor - Eric M. Jackson; Tamim H. Shaikh; Sridharan Gururangan; Marilyn C. Jones; David Malkin; Sarah M. Nikkel; Craig W. Zuppan; Luanne M. Wainwright; Fan Zhang; Jaclyn A. Biegel (Human Genetics, 2007)

Optimizing carbon sequestration in commercial forests by integrating carbon management objectives in wood supply modeling - Charles P.-A. Bourque; Eric T. Neilson; Chris Gruenwald; Samantha F. Perrin; Jason C. Hiltz; Yvon A. Blin; Geoffrey V. Horsman; Matthew S. Parker; Christie B. Thorburn; Michael M. Corey; Fan-rui Meng; D. Edwin Swift (Mitigation and Adaptation Strategies for Global Change, 2007)

Mapping pre-European settlement vegetation at fine resolutions using a hierarchical Bayesian model and GIS - Hong S. He; Daniel C. Dey; Xiuli Fan; Mevin B. Hooten; John M. Kabrick; Christopher K. Wikle; Zhaofei Fan (Plant Ecology, 2007)

Electric Fields around and within Single Cells during Electroporation—A Model Study - Brian J. Mossop; Roger C. Barr; Joshua W. Henshaw; Fan Yuan (Annals of Biomedical Engineering, 2007)

Immunogenicity of Empty Capsids of Porcine Circovius Type 2 Produced in Insect Cells - H. Fan; C. Ju; T. Tong; H. Huang; J. Lv; H. Chen (Veterinary Research Communications, 2007)

A numerical study of the influence of urban expansion on monthly climate in dry autumn over the Pearl River Delta, China - W. S. Lin; C.-H. Sui; L. M. Yang; X. M. Wang; R. R. Deng; S. J. Fan; C. S. Wu; A. Y. Wang; S. K. Fong; H. Lin (Theoretical and Applied Climatology, 2007)

Elucidation of the mechanisms underlying the angiogenic effects of ginsenoside Rg1 in vivo and in vitro - Patrick Y. K. Yue; Daisy Y. L. Wong; W. Y. Ha; M. C. Fung; N. K. Mak; H. W. Yeung; H. W. Leung; Kelvin Chan; L. Liu; T. P. D. Fan; Ricky N. S. Wong (Angiogenesis, 2007)

Numerical comparison study of cloud microphysical parameterization schemes for a moderate snowfall event in North China - W. S. Lin; C.-H. Sui; C. Bueh; A. Wang; S. Fan; C. Wu; S. Fong; J. Li; J. Meng (Meteorology and Atmospheric Physics, 2007)

Electric Fields in Tumors Exposed to External Voltage Sources: Implication for Electric Field-Mediated Drug and Gene Delivery - Brian J. Mossop; Roger C. Barr; Joshua W. Henshaw; David A. Zaharoff; Fan Yuan (Annals of Biomedical Engineering, 2006)

Inorganic N Dynamics from Soils Amended with Low-P Manure from Genetically Modified Pigs (EnviropigTM) - X. M. Yang; C. F. Drury; T. Q. Zhang; A. Ajakaiye; C. W. Forsberg; M. Z. Fan; J. P. Philip (Nutrient Cycling in Agroecosystems, 2006)

Analysis of MS2Bnap genomic DNA homologous to MS2 gene from Arabidopsis thaliana in two dominant digenic male sterile accessions of oilseed rape (Brassica napus L.) - S. W. Hu; Y. F. Fan; H. X. Zhao; X. L. Guo; C. Y. Yu; G. L. Sun; C. H. Dong; S. Y. Liu; H. Z. Wang (Theoretical and Applied Genetics, 2006)

Facilitating Physiologic Self-Regeneration: A Step Beyond Islet Cell Replacement - Pleunie P. M. Rood; Rita Bottino; A. N. Balamurugan; Yong Fan; David K. C. Cooper; Massimo Trucco (Pharmaceutical Research, 2006)

Radon distribution in groundwater of Taiwan - Y. L. Han; M. C. Tom Kuo; K. C. Fan; C. J. Chiang; Y. P. Lee (Hydrogeology Journal, 2006)

A preliminary geological and geochemical study of the Xiangquan thallium deposit, eastern China: the world’s first thallium-only mine - T. F. Zhou; Y. Fan; F. Yuan; M. A. Wu; M. J. Hou; G. Voicu; Q. H. Hu; Q. M. Zhang; S. C. Yue (Mineralogy and Petrology, 2005)

Wide variation in the cyanobacterial complement of presumptive penicillin-binding proteins - Francisco Leganés; Amaya Blanco-Rivero; Francisca Fernández-Piñas; Miguel Redondo; Eduardo Fernández-Valiente; Qing Fan; Sigal Lechno-Yossef; C. Peter Wolk (Archives of Microbiology, 2005)

Single-nucleotide polymorphisms in the C-reactive protein (CRP) gene promoter that affect transcription factor binding, alter transcriptional activity, and associate with differences in baseline serum CRP level - A. J. Szalai; J. Wu; E. M. Lange; M. A. McCrory; C. D. Langefeld; A. Williams; S. O. Zakharkin; V. George; D. B. Allison; G. S. Cooper; F. Xie; Z. Fan; et al. (Journal of Molecular Medicine, 2005)

The main effects, epistatic effects and environmental interactions of QTLs on the cooking and eating quality of rice in a doubled-haploid line population - C. C. Fan; X. Q. Yu; Y. Z. Xing; C. G. Xu; L. J. Luo; Qifa Zhang (Theoretical and Applied Genetics, 2005)

Immunocytochemical localization of gonadotropins during the development of XX and XY Nile tilapia - F. Sakai; I. Swapna; C. C. Sudhakumari; M. V. N. L. Ganesh; H. Kagawa; T. Kobayashi; H. Fan; Y. Nagahama; B. Senthilkumaran (Fish Physiology and Biochemistry, 2005)

Timing of larval release by the blue coral, Heliopora coerulea, in southern Taiwan - P. J. Liu; T. Y. Fan; C. F. Dai (Coral Reefs, 2005)

Variation in gas exchange and water use efficiency patterns among populations of western redcedar - Steven C. Grossnickle; Shihe Fan; John H. Russell (Trees, 2005)

Screening marine algae from China for their antitumor activities - Nianjun Xu; Xiao Fan; Xiaojun Yan; C. K. Tseng (Journal of Applied Phycology, 2004)

Evaluation of the U.S. Navy’s Modular Ocean Data Assimilation System (MODAS) Using South China Sea Monsoon Experiment (SCSMEX) Data - Peter C. Chu; Wang Guihua; Chenwu Fan (Journal of Oceanography, 2004)

A Terrain-Following Crystal Grid Finite Volume Ocean Circulation Model - Peter C. Chu; Chenwu Fan (Journal of Oceanography, 2004)

p53 dephosphorylation and p21Cip1/Waf1 translocation correlate with caspase-3 activation in TGF-β1-induced apoptosis of HuH-7 cells - G. Fan; X. Ma; P. Y. Wong; C. M. P. Rodrigues; C. J. Steer (Apoptosis, 2004)

Combining carbon sequestration objectives with timber management planning - Fan-Rui Meng; Charles P.-A. Bourque; Steven P. Oldford; D. Edwin Swift; Helen C. Smith (Mitigation and Adaptation Strategies for Global Change, 2003)

Molecular characterization of a distinct potyvirus from whitegrass in China - Z. Fan; H. Chen; S. Cai; C. Deng; W. Wang; X. Liang; H. Li (Archives of Virology, 2003)

Analysis of Pollutant Levels in Central Hong Kong Applying Neural Network Method with Particle Swarm Optimization - W. Z. Lu; H. Y. Fan; A. Y. T. Leung; J. C. K. Wong (Environmental Monitoring and Assessment, 2002)

Low Salinity, Cool-Core Cyclonic Eddy Detected Northwest of Luzon during the South China Sea Monsoon Experiment (SCSMEX) in July 1998 - Peter C. Chu; Chenwu Fan (Journal of Oceanography, 2001)

Molecular Cloning of cgrA, the Gene Encoding the Aspergillus nidulans Ortholog of Saccharomyces cerevisiae CGR1 - Jianlan Sun; Douglas Boettner; Nichole Huebner; Fan Xu; Judith C. Rhodes; David S. Askew (Current Microbiology, 2001)

Mutation analysis of hereditary multiple exostoses in the Chinese - L. Xu; J. Xia; H. Jiang; J. Zhou; H. Li; D. Wang; Q. Pan; Z. Long; C. Fan; H.-X. Deng (Human Genetics, 1999)

The role of retinoblastoma protein in apoptosis - G. Fan; C. J. Steer (Apoptosis, 1999)

P-Vector inverse method evaluated using the modular ocean model (MOM) - Peter C. Chu; Chenwu Fan; Wenju Cai (Journal of Oceanography, 1998)

Quantification of the repair process involved in the repair of a cell monolayer using an in vitro model of mechanical injury - Heather Lauder; Emma E. Frost; C. Robin Hiley; Tai-Ping D. Fan (Angiogenesis, 1998)

Transgenic fertile japonica rice plants expressing a modified cryIA(b) gene resistant to yellow stem borer - C. Wu; Y. Fan; C. Zhang; N. Oliva; S. K. Datta (Plant Cell Reports, 1997)

AZT blocks down-regulation of IL-2 and IFN-γ gene expression in HIV acutely infected cells - J. Fan; P. Li; T.-W. Kok; C. J. Burrell (Archives of Virology, 1997)

Conditional, tissue-specific expression of Q205L G αi2 in vivo mimics insulin action - Jiang Fan Chen; Jun Hua Guo; Christopher M. Moxham; Hsien-yu Wang; C. C. Malbon (Journal of Molecular Medicine, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Correlation of guanosine triphosphate cyclohydrolase activity and the synthesis of pterins in Drosophila melanogaster - C. L. Fan; L. M. Hall; A. J. Skrinska; G. M. Brown (Biochemical Genetics, 1976)